Absorption loss influence on optical characteristics of multilayer distributed Bragg reflector: Wavelength-scale analysis by the method of single expression - Baghdasaryan, H. V.; Knyazyan, T. M.; Baghdasaryan, T. H.; Witzigmann, Bernd; Roemer, F. (Opto-Electronics Review, 2010)
Electrodynamical model of a classical distributed Bragg reflector (DBR) consisting of alternating quarter-wave layers of high and low permittivity is considered at the plane wave normal incidence. Reflective characteristics of DBR possessing absorption loss in constituting layers are analysed via correct wavelength-scale boundary problem solution by the method of single expression (MSE). Analysis of optical field and power flow density distributions within the lossy DBR structures explained the peculiarities of their reflective characteristics. Optimal configurations of lossless and lossy DBRs are revealed. Specific DBR structures possessing full transparency at definite number of layers are also analysed. © 2010 Versita Warsaw and Springer-Verlag Wien.
CRIS-Team Scopus Importer:2021-06-11
Keywords: boundary problem solution; lossy DBR; method of single expression (MSE); optical field distribution; quarter-wave layers; transparent DBR; wavelength-scale analysis

Acceptor activation model for III-nitride LEDs - Roemer, Friedhard; Witzigmann, Bernd (Journal of Computational Electronics, 2015)
One major contribution to the decay of the internal quantum efficiency (IQE) of InGaN/GaN light emitting diodes (LED) at high current densities is the direct carrier leakage. The direct carrier leakage is mainly caused by electron leakage and is therefore strongly affected by the design of the p-region. In this context we investigate the effect of the acceptor doping on the efficiency. Since acceptor impurities in GaN based materials are subject to a high activation energy we discuss the electronic activation mechanisms as well as activation barrier reduction phenomena. By physics based simulation of a GaN-based LED we demonstrate that the processes reducing the acceptor activation energy affect the IQE and the bias voltage characteristics. We show that by designing the acceptor doping profile the efficiency of GaN-based thin film LEDs may be enhanced.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Acceptor doping; Efficiency; Gallium nitride; Light emitting diode; Simulation

Acceptor impurity activation in III-nitride light emitting diodes - Roemer, Friedhard; Witzigmann, Bernd (Applied Physics Letters, 2015)
In this work, the role of the acceptor doping and the acceptor activation and its impact on the internal quantum efficiency (IQE) of a Gallium Nitride (GaN) based multi-quantum well light emitting diode is studied by microscopic simulation. Acceptor impurities in GaN are subject to a high activation energy which depends on the presence of proximate dopant atoms and the electric field. A combined model for the dopant ionization and activation barrier reduction has been developed and implemented in a semiconductor carrier transport simulator. By model calculations, we demonstrate the impact of the acceptor activation mechanisms on the decay of the IQE at high current densities, which is known as the efficiency droop. A major contributor to the droop is the electron leakage which is largely affected by the acceptor doping.
CRIS-Team Scopus Importer:2021-06-11

A high efficiency dual-junction solar cell implemented as a nanowire array - Yu, Shuqing; Witzigmann, Bernd (Optics Express, 2013)
In this work, we present an innovative design of a dual-junction nanowire array solar cell. Using a dual-diameter nanowire structure, the solar spectrum is separated and absorbed in the core wire and the shell wire with respect to the wavelength. This solar cell provides high optical absorptivity over the entire spectrum due to an electromagnetic concentration effect. Microscopic simulations were performed in a three-dimensional setup, and the optical properties of the structure were evaluated by solving Maxwell’s equations. The Shockley-Queisser method was employed to calculate the current-voltage relationship of the dual-junction structure. Proper design of the geometrical and material parameters leads to an efficiency of 39.1%. © 2012 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-11

All-InGaN phosphorless white light emitting diodes: An efficiency estimation - Koelper, Christopher; Sabathil, Matthias; Mandl, Martin; Strassburg, Martin; Witzigmann, Bernd (Journal of Lightwave Technology, 2012)
In this theoretical study we investigate the efficiency potential of monolithic white light emitting diodes (LEDs) that are free of wavelength-converting phosphors and are based solely on the InGaN material system. For that purpose we develop a numerical model that handles multiple active layers of different emission wavelength and takes photon reabsorption and-emission as well as internal non-radiative and optical losses into account. It is applied both to thin film structures as well as novel nanorod LEDs featuring disc-like active layers. In both cases, the active layers may either consist of multiple thin quantum wells or a single thick, bulk-like InGaN layer. © 2012 IEEE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Efficiency droop; GaN; LED; nanorods; nitrides; photon recycling; white light

Analysis of effective carrier mobility in the multi-quantum wells of DUV AlGaN LEDs by carrier transport simulations - Alhussien Ali Marouf, Ibrahim; Römer, Friedhard; Schilling, Marcel; Biebler, Franz; Höpfner, Jakob; Grigoletto, Massimo; Wernicke, Tim; Kneissl, Michael; Witzigmann, Bernd (Proceedings Volume PC13360, Physics and Simulation of Optoelectronic Devices XXXIII, 2025)
AlGaN-based LEDs show promise in Deep Ultraviolet (DUV) emission for environmental and medical uses, but optimizing Carrier Injection Efficiency (CIE) is challenging. This study uses a microscopic simulation model to investigate the emission spectra of dual wavelength AlGaN LEDs. The model includes advanced features such as carrier transport dynamics, and radiative recombination processes. The simulations examine LEDs with varying Quantum Wells (QWs) emitting at 233 nm and 250 nm to understand carrier distribution. Results indicate that electron densities in the MQW stack are higher than hole densities, leading to an imbalance that affects CIE and optical spectr

Analysis of photonic crystal defect modes by maximal symmetrization and reduction - Gallinet, Benjamin; Kupec, J.; Witzigmann, Bernd; Dupertuis, M. -A. (Journal of the Optical Society of America B-Optical Physics, 2010)
We analyze in depth the eigenmodes symmetry of the vectorial electromagnetic wave equation with discrete symmetry, using a recently developed maximal symmetrization and reduction scheme leading to an automatic technique which decomposes every mode into its most fundamental internal geometrical components carrying independent symmetries, the ultimately reduced component functions (URCFs). Using URCFs, geometrical properties of photonic crystal defect modes can be analyzed in great details. In particular we analytically identify the kind of modes that display non-vanishing transverse electric or transverse magnetic amplitude at the cavity center in C 2v, C 3v, C 4v and C 6v symmetries, and their degeneracies. We also build a postprocessing tool able to extract and identify URCFs out of the modes whether from experimental or numerical origin. In the latter case it is independent of the eigenmode computation method. In another variant the whole eigenmode computation can be systematically reduced to a minimal domain, without any need for applying specific nontrivial boundary conditions. The approach leads to strong analytical predictions which are illustrated for specific H1 and L3 cavities using the postprocessing tool on full three-dimensional computed modes. It not only constitutes an unprecedented check of the symmetry of the computational results, but it is shown to also deliver a deep geometrical and physical insight into the structure of the modes of photonic bandgap microcavities, which is of direct use for most modern applications in quantum photonics. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-11

Analysis of semiconductor nanowire arrays for photovoltaics - Witzigmann, Bernd; Yu, Shuqing; Kupec, Jan (Proceedings - 2011 International Conference on Electromagnetics in Advanced Applications, ICEAA'11, 2011)
The electro-optical properties of nanowire array solar cells are analyzed with a microscopic simulation model. For the electromagnetic part, the vectorial Helmholtz equation is solved for the three-dimensional structure, and a modal analysis reveals the absorption mechanisms. The electronic part is analyzed with a drift-diffusion approach. It is shown that with a proper design, a III-V nanowire array solar cell can approach the efficiency of a thin-film solar cell, while only a fraction of the active material volume is used. © 2011 IEEE.
CRIS-Team Scopus Importer:2021-06-11

Analysis of surface-emitting thin-film superluminescent diodes with high efficiency - Jentzsch, Bruno; Gomez-Iglesias, Alvaro; Tonkikh, Alexander; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
In this paper, a novel surface-emitting superluminescent diode fabricated by applying full on-wafer processing is presented. The surface-emission is achieved via mirrors etched by using an inductively coupled plasma process. This geometry allows to deflect in-plane guided and amplified optical modes perpendicular to the chip surface. The out-coupling window is anti-reflection coated, while at the other end of the waveguide a high-reflecting coating was deposited. In this way the device uses double-pass amplification, increasing efficiency, and light is emitted from a single spot. The light propagation and out-coupling in the proposed concept are first theoretically analyzed. Moreover, in order to simulate the optical output power, a rate equation-based frequency-resolved model accounting for non-ideal facet reflectivities and lasing onset is introduced. Finally, the measured L-I and spectral characteristics of fabricated InGaAs/GaAs superluminescent diodes emitting at a peak wavelength of 960nm are presented and compared to simulation results. At room temperature, pulsed output powers up to ∼125mW with a FWHM of 14nm and a wall-plug efficiency higher than 10% were achieved.
CRIS-Team Scopus Importer:2021-06-11
Keywords: SLED; Superluminescent Diode; Surface-Emission; Thin Film Technology

Analysis of surface recombination in nanowire array solar cells - Yu, Shuqing; Roemer, Friedhard; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2012)
In this work, microscopic three-dimensional (3D) simulations were performed on nanowire array solar cells to study the impact of surface recombination on the photovoltaic performance. Both axially and radially arranged p-n junction in III-V based structures were taken into consideration. From the cases with surface recombination velocity varying from 1e3cm/s to 1e6cm/s, the core-shell nanowire was found to provide better tolerance for surface recombination. The difference of surface recombination within the axial and core-shell structures is explained by analyzing the relevent minority carrier density, followed by a discussion on the impact of surface recombination on the performance of nanowires as photovoltaic devices. © 2012 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Carrier transport properties; Nanowire; Photovoltaics; Semiconductor; Solar cell

Analysis of surface recombination in nanowire array solar cells - Yu, Shuqing; Roemer, Friedhard; Witzigmann, Bernd (Journal of Photonics for Energy, 2012)
In this work, microscopic three-dimensional simulations were performed on nanowire array solar cells to study the impact of surface recombination (SR) on the photovoltaic performance. Both axially and radially arranged p-n junction in III-V-based structures were taken into consideration. From the cases with SR velocity varying from 1e3 cm/s to 1e6 cm/s, the radial p-n-junction nanowire was found to provide better tolerance for SR. The SR difference within the axial and radial p-n-junction structures is explained by analyzing the relevant minority carrier density, followed by a discussion on the impact of SR on the diffusive nature of minority carriers. © 2012 Society of Photo-Optical Instrumentation Engineers (SPIE).
CRIS-Team Scopus Importer:2021-06-11
Keywords: Carrier transport properties; Nanowire; Photovoltaics; Semiconductor; Solar cell

Auger carrier leakage in III-nitride quantum-well light emitting diodes - Deppner, Marcus; Roemer, Friedhard; Witzigmann, Bernd (Physica Status Solidi-Rapid Research Letters, 2012)
Auger induced leakage is shown to be a contributing factor for the internal quantum efficiency (IQE) droop in III-nitride quantum-well light emitting diodes (LEDs). The mechanism is based on leakage current from carrier spill-out of the well originating from energy transfer during Auger recombination. Adding this leakage reduces the Auger coefficient by 50% when compared to a standard Auger model with cubic density dependence. As reference, experimental data of a green quantum-well LED are taken. Direct leakage due to non-ideal carrier capture and re-emission out of the well affects the IQE at current densities much larger than the maximum IQE point. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Auger recombination; GaN; Light emitting diodes; Quantum efficiency

Auger recombination and carrier transport effects in III-nitride quantum well light emitting diodes - Deppner, Marcus; Roemer, Friedhard; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2013)
Gallium nitride based light emitting diodes (LEDs) have established as powerful devices, that are well suited for general lighting. Despite the progress within the recent years the so-called "efficiency droop" is still a central issue of nitride-based LED research. Up to now, no widely accepted explanation is available for the reduction of the internal quantum efficiency with increasing injection current. We report on a novel mechanism contributing to efficiency droop, that combines two of the previously reported effects: Auger recombination and carrier leakage. A sophisticated Auger model, that takes account of the overlap of the wave functions, is extended to model the energy transfer towards the third involved carrier. This carrier is assumed to be expelled from the well and regenerated in the continuum carrier population, where it can contribute to carrier leakage. A physics-based simulation of a quantum well LED employing a semi-classical approach has been carried out to demonstrate the impact of this effect. Depending on the parametrization, the inclusion of Auger expulsion reduces the Auger coefficient up to 50% when compared to a standard Auger model, which could explain the discrepancy between calculated and experimentally extracted Auger coefficients. © 2013 Copyright SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Auger; compound semiconductors; computational modeling; droop; GaN; InGaN; leakage; LEDs; physics-based simulation; solid-state lighting

Auger recombination and leakage in InGaN/GaN quantum well LEDs - Roemer, Friedhard; Deppner, Marcus; Range, Christian; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
The efficiency of blue InGaN/GaN light emitting diodes (LEDs) for solid state lighting has been strongly increased in the past years. The decay of the internal quantum efficiency at current densities above 100 Acm-2 remains, though. This effect is known as droop and effectively limits the maximum current density. The physical mechanisms behind the droop are not yet fully understood. Theories for the origin of the droop include the Auger recombination process and direct carrier leakage. In this context we present an analysis of the contribution of these effects to the droop by means of physics based simulation. In contrast to lumped simulation models the physical simulation model presented in this work enables the exact matching of the internal quantum efficiency (IQE) characteristics by including the geometry, doping, and mole fraction profiles. The analysis presented in this work uses the IQE data of a fabricated blue single quantum well LED. Fitting this IQE curve with the physics based simulation enables the estimation of limits for the Auger coefficients as well as the contribution of the direct carrier leakage. Including Auger assisted carrier leakage facilitates fitting the IQE with reduced Auger coefficients closing the gap to atomistic simulations. © 2014 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Auger recombination; droop; gallium nitride; internal quantum efficiency; leakage; light emitting diode; simulation

Auger recombination and leakage in InGaN/GaN quantum well LEDs - Römer, Friedhard; Witzigmann, Bernd; Deppner, Marcus; Range, Christian (Gallium Nitride Materials and Devices IX, 2014)
Keywords: simulation; droop; Auger recombination; internal quantum efficiency; gallium nitride; light emitting diode; leakage

Beam quality optimization of electrically pumped VECSELs for passive modelocking - Pallmann, W. P.; Hoffmann, M.; Miller, M.; Baier, J.; Moench, H.; Dahhan, I.; Witzigmann, Bernd; Golling, M.; Barbarin, Yohan; Suedmeyer, T.; Keller, Ursula (Proceedings of SPIE - The International Society for Optical Engineering, 2011)
Fundamental mode operation along with high output power is a major challenge for an electrically pumped VECSEL (EP-VECSEL) suitable for passive modelocking. We present an experimental study on the influence of the intermediate DBR reflectivity on the beam quality and the output power of EP-VECSELs. For designs with reflectivities of 90%, 82% and 71% the highest possible power for the best achievable beam quality was 15.1 mW (M2 = 1.1, 82% device). We can demonstrate that a correctly chosen intermediate DBR reflectivity is necessary for both good beam quality and high power, and that a trade-off in power has to be accepted.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Electrical pumping; Passive modelocking; Semiconductor lasers; Vertical emitting lasers

Calculation of optical eigenmodes and gain in semipolar and nonpolar InGaN/GaN laser diodes - Scheibenzuber, W. G.; Schwarz, U. T.; Veprek, R. G.; Witzigmann, Bernd; Hangleiter, Andreas (Physical Review B, 2009)
We investigate the anisotropic optical gain in non- c -plane InGaN quantum wells with 20% indium content including band-gap renormalization and the screening of the quantum confined Stark effect. Waveguide modes and their polarizations are determined as TE and TM modes or extraordinary and ordinary modes, depending on the birefringence and the orientation of the laser diode's ridge waveguide relative to the c axis. The band structures and optical matrix elements along the polarization directions are calculated using a 6×6 kp Hamiltonian and a self-consistent Schrödinger-Poisson solver. From these calculations the reduced density of states and the optical gain for the different polarizations are determined in the free-carrier picture with an ad hoc inclusion of the band-gap renormalization and compared to a c -plane quantum well. It is found that for high indium concentrations the gain can be significantly increased by going from the c plane to a semipolar or a nonpolar crystal orientation. However, due to birefringence and composition of the topmost valence-band wave function, the ridge has to be oriented along the [1̄ 1̄ 23] direction for semipolar and along the [0001] direction for nonpolar laser diodes. © 2009 The American Physical Society.
CRIS-Team Scopus Importer:2021-06-11

Calculation of optical gain in AlGaN quantum wells for ultraviolet emission - Witzigmann, Bernd; Roemer, Friedhard; Martens, Martin; Kuhn, Christian; Wernicke, Tim; Kneissl, Michael (AIP Advances, 2020)
Stimulated emission from AlGaN based quantum wells (QWs) emitting at ultraviolet wavelengths is investigated theoretically. Maxwell-Bloch equations in the second Born approximation are solved self-consistently with the Poisson equation. The valence band dispersion is obtained from a 6-band kp-model. For a QW emitting at around 270 nm with a thickness of 2.2 nm, an estimated FWHM of 10 meV for homogeneous broadening and an excitonic red shift of 100 meV are extracted under typical laser conditions. From a comparison to experimental data of stimulated emission, an inhomogeneous broadening energy of 39 meV FWHM is evaluated. Calculations show that high TE gain can be achieved for thin QWs around 2 nm thickness in a multiple QW arrangement or for single QWs thicker than 6 nm.
CRIS-Team Scopus Importer:2021-06-11

Carrier injection efficiency in III-nitride light emitting diodes: Effective potential correction - Witzigmann, Bernd; Romer, Friedhard (Optics InfoBase Conference Papers, 2020)
A model for carrier injection efficiency of III-nitride based light emitters with multiple quantum wells is described. With a combination of semi-classical and quantum transport, it matches a wide range of experimental LED data for solid-state lighting.
CRIS-Team Scopus Importer:2021-06-11

Carrier Transport in a Deep Ultraviolet Mixed Quantum Well Light Emitting Diode - Römer, Friedhard; Hofmann, Gregor; Hoopfner, Jakob; Schilling, Marcel; Muhin, Anton; Wernicke, Tim; Kneissl, Michael; Witzigmann, Bernd (IEEE Photonics Journal, 2024)
Aluminium Gallium Nitride (AlGaN) based light emitting diodes (LED) are the enabling technology for compact emitters of deep ultraviolet (DUV) radiation and are in high demand for environmental and medical applications. The efficiency of recent DUV LEDs is in the range of a few percent providing some potential for improvement. Apart from the light extraction efficiency the hole injection into the active region presents a major obstacle towards more efficient DUV LEDs. In this work, we investigate the emission spectra of a mixed multi quantum well (MQW) DUV LED to attain details on the active region carrier transport that allow an improvement of the hole injection. Changing the position of the long wavelength marker quantum well yields characteristic emission spectra which have been modelled with a multi scale carrier transport and luminescence simulator. The numerical modelling enables the extraction of opaque carrier transport characteristics in AlGaN such as the hole mobility in the highly doped barriers of the MQW.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Aluminum gallium nitride; carrier transport; Charge carrier processes; deep ultraviolet; III-Nitride; Light emitting diode; Light emitting diodes; Mathematical models; numerical modelling; Quantum well devices; Radiative recombination; Wide band gap semiconductors

Carrier Transport in Multi Colour Deep Ultraviolet Light Emitting Diodes - Hofmann, Gregor; Höpfner, J.; Schilling, M.; Muhin, A.; Romer, F.; Wernicke, T.; Kneissl, M.; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2022)
Deep ultraviolet (DUV) light emitting diodes (LEDs) and lasers are enabled by high band gap Aluminium Gallium Nitride (AlGaN). The efficiency of recent multi quantum well (MQW) DUV emitters is still in the percent range which can be in part attributed to the hole injection. The hole injection and the carrier distribution in the high band gap AlGaN active region are not yet well understood. To support the experimental investigation of the current injection and distribution we have performed numerical simulations of a mixed MQW DUV LED series emitting at 233nm and 250 nm. We demonstrate that particularly the emission of the 233nm quantum well is very sensitive to the AlGaN material properties and inhomogeneous broadening. The numerical modelling enables a better interpretation of experimental data.
CRIS-Team Scopus Importer:2022-10-21

Carrier transport in the multi quantum well region of III-nitride light emitting diodes - Romer, Friedhard; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2017)
The carrier transport in the multi quantum well (MQW) region of Ill-nitride light emitting diodes is critical for their efficiency in the high current regime. The asymmetry of the electron and hole transport makes it difficult to achieve an equal distribution of the quantum well luminescence in order to decrease the droop. To study the luminescence distribution we have devised a carrier transport model accounting for the carrier quantization effects in an MQW active region. The detailed study of the carrier distribution in the MQW is supported by an equivalent circuit model. By means of this model we demonstrate that the re-distribution of the luminescence in the MQW with increasing bias current has an effect on the ideality factor.
CRIS-Team Scopus Importer:2021-06-11

CMOS-compatible optical switching concept based on strain-induced refractive-index tuning - Virgilio, Michele; Witzigmann, Bernd; Bolognini, Gabriele; Guha, Subhajit; Schroeder, Thomas; Capellini, Giovanni (Optics Express, 2015)
In this paper we present a planar lightwave switching mechanism based on large refractive index variations induced by electrically-driven strain control in a CMOS-compatible photonic platform. Feasibility of the proposed concept, having general validity, is numerically analyzed in a specific case-study given by a Mach-Zehnder Interferometer with Ge waveguides topped by a piezoelectric stressor. The stressor can be operated in order to dynamically tune the strain into the two interferometric arms. The strain modifies the Ge band structure and can induce refractive index variations up to 0.05. We demonstrate that this approach can enable ultracompact devices featuring low loss propagation for light wavelengths below the waveguide band gap energy, high extinction ratios (>30 dB) and low intrinsic insertion losses (2 dB). The operation wavelength can be extended in the whole FIR spectrum by using SiGe(Sn) alloy waveguides.
CRIS-Team Scopus Importer:2021-06-11

Comprehensive modeling of optoelectronic nanostructures - Witzigmann, Bernd; Veprek, Ratko G.; Steiger, Sebastian; Kupec, Jan (Journal of Computational Electronics, 2009)
This paper gives an overview of physics-based modeling of optoelectronic nanostructures, driven by diverse applications such as photovoltaics, solid-state lighting, communications and sensing. Despite this broad field of applications, some common challenges can be identified: accurate modeling of light-matter interaction, semi-coherent carrier transport in the presence of strong recombination, calculation of material properties and electromagnetic characteristics. In this contribution, the general purpose simulation framework tdkp/AQUA/LUMI is presented, with the focus on non-planar nanowire devices. © 2009 Springer Science+Business Media LLC.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Light emitting diodes; Optoelectronics; Photovoltaics; Simulation

Computational electromagnetics for nanowire solar cells - Kupec, Jan; Witzigmann, Bernd (Journal of Computational Electronics, 2012)
This review article provides an overview of various novel nanowire array solar cells and highlights the aspects of electromagnetic simulations that are a valuable tool for understanding the optical processes leading to their distinct properties. As the computational methods commonly used for the task are well established, we focus on the question how numerical modeling can be used to assess the performance of a design and reveal the working principle of the devices. We conclude that scientific literature identifies numerical simulations as paramount for design and interpretation of experimental data. © Springer Science+Business Media LLC 2012.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Absorption enhancement; Detailed balance; Electromagnetics; Emission; FDTD; Finite element; Light trapping; Nanowire; Solar cell

Computational modelling of surface effects in InGaN/GaN quantum disk nano wire LEDs - Roemer, Friedhard; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2013)
One focus of the current research on light emitting diodes (LEDs) for lighting are nano structured devices which are expected to improve the efficiency and reduce the production costs. Structuring on the sub-micrometer scale increases the surface area with respect to the active volume so that surface effects have a large impact on the device performance. The physics of these devices is not fully transparent to characterization making an experimental analysis tedious. In this work we demonstrate the computational modelling of nano structured LEDs to complement the experiment. The implementation of the simulation model considers surface effects using a numerically accurate true area box method discretization. The derived surface models are applied to the self-consistent simulation of nano wire quantum disk light emitting diodes. By the computational study we demonstrate that the surface physical effects are critical for the performance of nano structured optoelectronic devices and that a low efficiency may be fully attributed to surface recombination. © 2013 Copyright SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Computational Electronics; Gallium Nitride; Light Emitting Diode; Nano Structure; Surface Effects

Computational modelling of surface effects in InGaN/GaN quantum disk nano wire LEDs - Römer, Friedhard; Witzigmann, Bernd (Physics and Simulation of Optoelectronic Devices XXI, 2013)
Keywords: Computational Electronics; Light Emitting Diode; Gallium Nitride; Surface Effects; Nano Structure

Computational optoelectronics as analysis and design tool - Witzigmann, Bernd (Symposium Digest - 20th URSI International Symposium on Electromagnetic Theory, EMTS 2010, 2010)
This paper gives an overview of physics-based modeling of semiconductor optoelectronic devices, which are key components in fields such as photovoltaics, solid-state lighting, communications and sensing. Despite this broad application range, some common underlying theory can be identified: accurate modeling of light-matter interaction, semi-coherent carrier transport in nanostructures, accurate calculation of electromagnetic characteristics. In this contribution, a selection of models and devices are discussed and their applicability for analysis purposes is demonstrated © 2010 IEEE.
CRIS-Team Scopus Importer:2021-06-11

Computational study of an InGaN/GaN nanocolumn light-emitting diode - Boecklin, Christoph; Veprek, Ratko G.; Steiger, Sebastian; Witzigmann, Bernd (Physical Review B, 2010)
A comprehensive three-dimensional analysis of the operation of an In0.4 Ga0.6 N/GaN nanocolumn light-emitting diode is presented. Focus is put on the investigation of the nature and location of the emitting states. Calculations of strain and polarization-induced internal fields show that the strong lateral dependence of the potential gives rise to states confined to the periphery and to the center of the nanocolumn. However, lateral confinement of states near the column center is weak such that a quantum-well-like treatment of the remaining bound states seems appropriate where coherence is lost in the lateral directions. Within this picture, a coupled and self-consistent three-dimensional simulation of carrier transport and luminescence is presented, thus accounting for screening and lateral transport effects. Results are compared to a planar quantum-well device. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2021-06-11

Computational study of carrier injection in III-nitride core-shell nanowire-LEDs - Deppner, Marcus; Römer, Friedhard; Witzigmann, Bernd; Ledig, Johannes; Neumann, Richard; Waag, Andreas; Bergbauer, Werner; Strassburg, Martin (IEEE - 2011 Semiconductor Conference Dresden: Technology, Design, Packaging, Simulation and Test, SCD 2011 - International Conference, Workshop and Table-Top Exhibition, 2011)
We report on the computational analysis of a core-shell GaN/InGaN nanowire LED with a capped pyramidal top. The active region consists of a polar multi quantum well (MQW) at the top, a non-polar MQW along the lateral face and a semi-polar one joining them. Differences in the opto-electronic characteristics of the three crystal orientations can be examined, arising from polarization effects as well as the strain-induced bandedge shift. Furthermore the influence of carrier injection efficiency in a nanowire is investigated. © 2011 IEEE.
CRIS-Team Scopus Importer:2021-06-11

Computational study of multi-color InGaN/GaN nanowire LEDs with continuously varied Indium composition - Deppner, Marcus; Bjelica, Marko; Roemer, Friedhard; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2012)
Gallium nitride based light emitting diodes have emerged as powerful devices which could replace incandescent and fluorescent lamps within the next years. The development of phosphor-free white LEDs is an ongoing field of research because of the lack of high efficiency green LEDs. A promising approach is the growth of InGaN/GaN nanowires with a continuously varied Indium content along the structure. The graded mole fraction profile is supposed to yield a multitude of emission colors due to many emission levels which can sum up to white light emission. The formation of strain and polarization charges is reduced because of the incremental varying lattice constants in combination with the facility of lateral relaxation of the wire. We report on the computational analysis of those nanowire structures in order to understand the electroluminescent behavior. The simulation software calculates the electrostatic potential and the carrier densities in the entire structure by solving the Poisson and the drift/diffusion equations in three dimensions. The luminescence is determined on the basis of a free carrier theory and enters the continuity equations as recombination term with strain and polarization effects included. This comprehensive physical model is employed to analyze carrier injection and luminescence for a white light-emitter design. © 2012 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Compound semiconductors; Computational modeling; GaN; InGaN; LEDs; Luminescence; Nanowires; Physics-based simulation; Solid-state lighting; Strain

Core-shell InGaN nanorod light emitting diodes: Electronic and optical device properties - Koelper, Christopher; Sabathil, Matthias; Roemer, Friedhard; Mandl, Martin; Strassburg, Martin; Witzigmann, Bernd (physica status solidi (a), 2012)
In this theoretical study, we investigate both electronic and optical properties of core-shell InGaN nanorods (NRs) for light emitting diodes (LEDs). These structures feature active layers wrapped around high aspect ratio NR cores, thus allowing for an enormous increase in active area. Hence, efficiency may be increased by operating at lower carrier densities, mitigating efficiency droop known to limit conventional InGaN LEDs. Due to poor conductivity of the outer pGaN shell, current spreading along the entire NR length is challenging and requires an additional cover of transparent conductive oxide in order to fully exploit the active area. At the same time, quantum wells (QWs) on core-shell NRs are grown on m-plane rather than conventional c-plane GaN facets. The calculations show that the absence of piezoelectric fields on these non-polar facets results in strong reabsorption of the emitted photons. A comprehensive numerical model is applied, linking internal quantum efficiency (IQE) and light extraction via the process of photon recycling. In summary, increasing optical absorption and photon recycling losses limit extraction efficiency. While this partially compensates the gain in IQE with increasing active area, a net improvement of the external quantum efficiency (EQE) of +10% is achievable by the proposed design of a novel core-shell NR LED. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2021-06-11
Keywords: efficiency droop; III-nitride semiconductors; InGaN; light-emitting diodes; nanorods

Current confinement in EP-VECSELs for high power single-mode operation suitable for passive mode-locking - Dahhan, Imad; Barbarin, Yohan; Hoffmann, Martin; Pallmann, Wolfgang P.; Zaugg, Christian; Golling, Matthias; Suedmeyer, Thomas; Keller, Ursula; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2012)
One of the main advantages of using VECSEL lasers for mode-locked operation is their power scalability. Best performance data available for mode-locked semiconductor lasers have been achieved with optically pumped VECSELs, reaching pulses in the femtosecond regime and average powers in the watt regime.1 This advantage is challenging for electrically pumped VECSELs, where a homogeneous carrier injection into the center must be provided in order to maintain a single-mode operation for large diameter devices. In this paper we investigate the current injection from the bottom contact of a VECSEL design, and estimate the leakage of the hole current. Then we introduce two designs that can reduce the leakage current and enhance the injection into the center of the device, thereby increasing the simulated output power by more than 20% in CW-mode while maintaining an optimal gain profile suitable for single-mode operation. © 2012 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Electrically-pumped; Mode-locking; Semiconductor laser; Simulation; VECSEL

Demonstration of UV-Induced Threshold Voltage Instabilities in Vertical GaN Nanowire Array-Based Transistors - Ruzzarin, Maria; Meneghini, Matteo; De Santi, Carlo; Neviani, Andrea; Yu, Feng; Strempel, Klaas; Fatahilah, Muhammad Fahlesa; Witzigmann, Bernd; Wasisto, Hutomo Suryo; Waag, Andreas; Meneghesso, Gaudenzio; Zanoni, Enrico (IEEE Transactions on Electron Devices, 2019)
This paper investigates the degradation of vertically aligned gallium nitride (GaN) nanowire (NW) arrays submitted to gate bias stress and UV light. Based on electrical tests and simulations, we demonstrate the existence of trapping processes that depend on the applied stress voltage VGstress and on the applied light during stress (wavelength, λ). We demonstrate the following original results: 1) for positive and negative VGstress conditions, no significant variation in dc characteristics is observed when the samples are stressed in dark and 2) when the devices are submitted to negative VGstress and to UV light, a positive variation in threshold voltage Vth) is observed. The positive Vth) shift is ascribed to the transfer and trapping of electrons from the gate metal to the oxide, promoted by UV light. We also evaluated the temperature dependence of the threshold voltage shift under UV light. We demonstrated an increased trapping at higher temperatures, indicating a role of thermionic processes in electron trapping. On the other hand, detrapping from oxide states proceeds through defect-mediated conduction, i.e., is limited by the number of available states.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Gallium nitride (GaN); MOS; nanowire (NW) transistor; threshold voltage; UV illumination; vertical electronics

Design and analysis of polarization selective tunable photonic crystal filters - Akcakoca, Ugur; Witzigmann, Bernd; Zamora, Ricardo; Kusserow, Thomas; Hillmer, Hartmut (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2011)
Our goal in this work is to achieve a tunable photonic crystal micro-opto-electro-mechanical system which excites two resonances with opposite polarization. In order to get a polarization selectivity we use two-dimensional photonic crystals with periodically arranged elliptical holes. We investigate the tunability and make statements about parameters that play an important role in optimization of this system. A final design is found for our goal. For the computation we use a three-dimensional finite element solver which solves the inhomogeneous Helmholtz equation. © 2011 IEEE.
CRIS-Team Scopus Importer:2021-06-11

Design and simulation of electrically pumped mode-locked VECSELs - Witzigmann, Bernd; Dahhan, Imad; Kreuter, Philipp; Barbarin, Yohan; Hofmann, Martin; Pallmann, Wolfgang; Golling, Mattthias; Suedmeyer, Thomas; Keller, Ursula (Proceedings of SPIE - The International Society for Optical Engineering, 2011)
Vertical External Cavity Surface Emitting Lasers (VECSELs) feature scaling to large active areas and combine surface emission with high optical power output. In principle, they can be designed with electrical pumping operating in continuous wave or passively mode-locked operation. In this paper, our design and modeling activities towards a high power passively mode-locked VECSEL are described. In particular, design towards single mode high-power CW operation is discussed as prerequisite for passive mode-locking.
CRIS-Team Scopus Importer:2021-06-11
Keywords: External cavity laser; Semiconductor laser; Simulation

Determination of polarization fields in group III-nitride heterostructures by capacitance-voltage-measurements - Rychetsky, Monir; Koslow, Ingrid; Avinc, Baran; Rass, Jens; Wernicke, Tim; Bellmann, Konrad; Sulmoni, Luca; Hoffmann, Veit; Weyers, Markus; Wild, Johannes; Zweck, Josef; Witzigmann, Bernd; et al. (Journal of Applied Physics, 2016)
The polarization fields in wurtzite group III-nitrides strongly influence the optical properties of InAlGaN-based light emitters, e.g., the electron and hole wave function overlap in quantum wells. In this paper, we propose a new approach to determine these fields by capacitance-voltage measurements (CVM). Sheet charges generated by a change of the microscopic polarization at heterointerfaces influence the charge distribution in PIN junctions and therefore the depletion width and the capacitance. We show that it is possible to determine the strength and direction of the internal fields by comparing the depletion widths of two PIN junctions, one influenced by internal polarization fields and one without as a reference. For comparison, we conducted coupled Poisson/carrier transport simulations on the CVM of the polarization-influenced sample. We also demonstrate the feasibility and limits of the method by determining the fields in GaN/InGaN and GaN/AlGaN double heterostructures on (0001) c-plane grown by metal organic vapor phase epitaxy and compare both evaluation methods. The method yields (-0.50 ± 0.07) MV/cm for In0.08Ga0.92N/GaN, (0.90 ± 0.13) MV/cm for Al0.18Ga0.82N/GaN, and (2.0 ± 0.3) MV/cm for Al0.31Ga0.69N/GaN heterostructures.
CRIS-Team Scopus Importer:2021-06-11

Dispersion, Wave Propagation and Efficiency Analysis of Nanowire Solar Cells - Kupec, J.; Witzigmann, Bernd (Optics Express, 2009)
We analyze the electromagnetic properties of InP/InAs nanowire solar cells for different geometries. We address both eigenvalue calculations to determine the wave propagation as well as source problems to simulate direct perpendicular illumination by three-dimensional finite element calculations. We demonstrate the validity of a 2D waveguide modal analysis as a method of estimating the results of the computationally far more demanding 3D analysis. The resulting data is employed in a detailed balance analysis in order to determine the optimum set of bandgap energies for a single-junction and dual-junction cell as well as the corresponding efficiency limit. The efficiency of the nanowire design can approach the efficiency of conventional thin-film designs despite the low volume fill-factor. © 2009 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-11

Effect of Auger recombination and leakage on the droop in InGaN/GaN quantum well LEDs - Roemer, Friedhard; Witzigmann, Bernd (Optics Express, 2014)
We investigate the effect of the epitaxial structure and the acceptor doping profile on the efficiency droop in InGaN/GaN LEDs by the physics based simulation of experimental internal quantum efficiency (IQE) characteristics. The device geometry is an integral part of our simulation approach. We demonstrate that even for single quantum well LEDs the droop depends critically on the acceptor doping profile. The Auger recombination was found to increase stronger than with the third power of the carrier density and has been found to dominate the droop in the roll over zone of the IQE. The fitted Auger coefficients are in the range of the values predicted by atomistic simulations.
CRIS-Team Scopus Importer:2021-06-11

Effect of doping and impurities on the efficiency of III-nitride light emitting diodes - Römer, Friedhard; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2015)
The doping of GaN based light emitting diodes (LEDs) is critical for achieving a high internal quantum efficiency. The high acceptor activation energy in GaN makes the acceptor doping a challenging task. Moreover, impurities might act as unintentional doping affecting the carrier injection. We analyze doping and impurity effects in III-nitride LEDs by means of physics based simulation. In the view of the high acceptor activation energy an enhanced impurity activation model has been devised integrating the effect of proximate doping sites and the Poole-Frenkel effect. We show by the simulation of a multi quantum well LED how the doping and shallow impurities affect the efficiency.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Doping; Gallium nitride; Impurities; Light emitting diodes; Physics; Radiative recombination; Semiconductor process modeling

Effect of Inhomogeneous Broadening in Deep Ultraviolet Light Emitting Diodes - Romer, Friedhard; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2021)
Due to their small dimensions deep ultraviolet (DUV) light emitting diodes (LED) are highly attractive light sources for environmental and medical applications. DUV LEDs generate light in active quantum wells (QW) made of Aluminium Gallium Nitride. The QWs are not lattice matched to the substrate and only few monolayers thick making them susceptible to compound fluctuations seen through inhomogeneous broadening (IHB). In this work we analyze by means of self consistent carrier transport and luminescence simulations how the IHB affects the electronic operation and emission polarization of DUV LEDs. We demonstrate that the IHB affects both the internal quantum efficiency and the current versus voltage curve of DUV LEDs.
CRIS-Team Scopus Importer:2021-10-22

Effect of Inhomogeneous Broadening in Ultraviolet III-Nitride Light-Emitting Diodes - Römer, Friedhard; Guttmann, Martin; Wernicke, Tim; Kneissl, Michael; Witzigmann, Bernd (Materials, 2021)
In the past years, light-emitting diodes (LED) made of GaN and its related ternary compounds with indium and aluminium have become an enabling technology in all areas of lighting. Visible LEDs have yet matured, but research on deep ultraviolet (UV) LEDs is still in progress. The polarisation in the anisotropic wurtzite lattice and the low free hole density in p-doped III-nitride compounds with high aluminium content make the design for high efficiency a critical step. The growth kinetics of the rather thin active quantum wells in III-nitride LEDs makes them prone to inhomogeneous broadening (IHB). Physical modelling of the active region of III-nitride LEDs supports the optimisation by revealing the opaque active region physics. In this work, we analyse the impact of the IHB on the luminescence and carrier transport III-nitride LEDs with multi-quantum well (MQW) active regions by numerical simulations comparing them to experimental results. The IHB is modelled with a statistical model that enables efficient and deterministic simulations. We analyse how the lumped electronic characteristics including the quantum efficiency and the diode ideality factor are related to the IHB and discuss how they can be used in the optimisation process.
CRIS-Team WoS Importer:2022-01-21

Effect of oxygen impurities in semipolar III-nitride light emitting diodes - Roemer, Friedhard; Witzigmann, Bernd (physica status solidi (a), 2017)
We investigate the effect of oxygen impurities on the internal quantum efficiency of semipolar III-nitride light emitting diodes (LED) structures grown along the (2021) direction by means of carrier transport simulations. For the model calculations, realistic doping and impurity profiles obtained by secondary ion mass spectroscopy are used. We discuss the impact of the oxygen impurity density on the operation of the LED and the interaction of the donor-type oxygen impurities with the acceptor doping. It is shown that up to a certain oxygen concentration, no major degradation of the LED efficiency occurs and that with increasing oxygen impurity density the LED efficiency becomes more sensitive to variations of the acceptor doping profile. The independent variation of the oxygen concentration revealed that oxygen impurities are most critical in the electron blocking layer and the p-side barrier.
CRIS-Team Scopus Importer:2021-06-11
Keywords: gallium nitride; impurity; light emitting diode; transport simulation

Effect of the Hole Mobility on the Emission Spectrum of a Deep Ultraviolet Mixed Quantum Well Light Emitting Diode - Römer, Friedhard; Hofmann, Gregor; Höpfner, J.; Schilling, Marcel; Muhin, A.; Wernicke, Tim; Kneissl, Michael; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2023)
Deep ultraviolet (DUV) light emitting diodes (LED) have matured in the past years but their efficiency still provides space for improvement. Below 265nm emission wavelength the quantum efficiency has been found to decrease almost exponentially. This is commonly attributed to the low light extraction efficiency and the small internal quantum efficiency. Increasing the internal quantum efficiency in this regime requires a deep understanding of the physical processes in the active region. To this end, we investigate the emission spectra of a mixed quantum well DUV LED emitting at 233nm and 250nm wavelength by means of physics based simulations. By comparing the simulations with measured spectra we estimate figures of physical properties entering the carrier transport. In particular we localize the hole mobility in the doped Aluminium Gallium Nitride barriers of the active region.
CRIS-Team Scopus Importer:2023-11-10

Efficiency analysis of III-V axial and core-shell nanowire solar cells - Yu, Shuqing; Kupec, Jan; Witzigmann, Bernd (Journal of Computational and Theoretical Nanoscience, 2012)
Here we present an efficiency analysis of axial and core-shell nanowire array solar cells. A microscopic three-dimensional (3D) electro-optical simulation is applied to both device types, and it is found that the core-shell nanowire provides higher photocurrent and lower open circuit voltage than the axial nanowire. Based on the microscopic 3D calculation of the carrier collection mechanism inside the devices, we derive a Shockley equation modified by the active region concept. This simplified model is then applied to systematically study the relationship between efficiency and nanowire geometry. Copyright © 2012 American Scientific Publishers All rights reserved.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Nanophotonics; Nanowire; Optoelectronics; Photovoltaics; Simulation; Solar cell

Efficiency analysis of nano light emitting diodes - Witzigmann, Bernd (Proceedings - 2014 International Conference on Electromagnetics in Advanced Applications, ICEAA 2014, 2014)
Semiconductor light emitting diodes (LEDs) are light sources with the highest broadband electro-optical efficiency of any solid state device. They are an ideal choice for energy efficient lighting applications. In this paper, the light extraction efficiency of nano-LEDs is studied based on electromagnetic modeling. As main result, it is shown that the optical extraction efficiency analysis requires detailed knowledge of the electronic properties of the LED, such as internal quantum efficiency and local absorptivity. These properties are studied for a III-nitride based nanowire array LED.
CRIS-Team Scopus Importer:2021-06-11

Efficiency optimization and analysis of 808nm VCSELs with a full electro-thermal-optical numerical model - Engelhardt, Andreas P.; Kolb, Johanna S.; Roemer, Friedhard; Weichmann, Ulrich; Moench, Holger; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2015)
A high electro-optical conversion efficiency of a VCSEL (Vertical-Cavity Surface-Emitting Lasers) is one of the key requirements for their application in high power systems for heating, illumination and pumping applications. The substantial amount of degrees of freedom in the epitaxial and structural design of a VCSEL demands numerical guidance in form of technology computer aided design (TCAD) modeling for a straight forward and successful optimization of the devices. We set up a full electro-thermal optical model for the simulation of VCSEL devices. The electro-thermal part of the simulation follows a drift-diffusion model complemented by a customized, energy resolved, semi-classical carrier capture theory in the QW regions. Optical modes, eigensolutions of the vectorial electromagnetic wave equation, stem from a finite element vectorial solver. The electro-thermal and optical models are linked via the photon-rate equation using QW gain spectra (screened Hartree-Fock approximation) and iterated to self-consistency in a Gummel-type iteration scheme. For comparison and calibration, experimental reference data was extracted from oxide-confined, top-emitting VCSEL devices with an emission wavelength of 808 nm. Our simulations are in good agreement with the electro-optical characteristics of the experimental reference. With the calibrated, microscopic model, routes of design adjustment for efficiency optimization are explored. Exemplarily, the maximum VCSEL efficiency of the simulated reference design increases by 10% (absolute) when free hole absorption is switched off. Accordingly, with the combination of an electro-thermal and optical description, a balancing of the tradeoffs of pDBR doping towards reduced free carrier absorption results in a noteworthy efficiency improvement which is validated with experimental data.
CRIS-Team Scopus Importer:2021-06-11
Keywords: distributed Bragg reflector; efficiency optimization; electro-thermal-optical; free carrier absorption; high efficiency; semiconductor lasers; VCSEL

Electrically-pumped VECSELs suitable for passive modelocking: Design, simulation and characterization in continuous wave - Barbarin, Y.; Pallmann, W. P.; Hoffmann, M.; Dahhan, I.; Kreuter, P.; Golling, M.; Südmeyer, T.; Witzigmann, Bernd; Keller, U. (Conference Digest - IEEE International Semiconductor Laser Conference, 2010)
An ultrafast electrically-pumped VECSEL design requires adjustments between electrical resistance, optical losses, dispersion and cw output power. Validating our simulations with homogeneous current injection in large devices, 120 mW cw output power are generated. ©2010 IEEE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Passive modelocking; Semiconductor lasers; Vertical emitting lasers

Electrically pumped vertical external cavity surface emitting lasers suitable for passive modelocking - Barbarin, Yohan; Hoffmann, Martin; Pallmann, Wolfgang P.; Dahhan, Imad; Kreuter, Philipp; Miller, Michael; Baier, Johannes; Moench, Holger; Golling, Matthias; Suedmeyer, Thomas; Witzigmann, Bernd; Keller, Ursula (IEEE Journal of Selected Topics in Quantum Electronics, 2011)
Modelocked optically pumped vertical external cavity surface emitting lasers (VECSELs) have generated up to 6.4-W average power, which is higher than for any other semiconductor lasers. Electrical pumping of modelocked VECSELs is the next step toward a higher level of integration. With continuous wave (cw) electrically pumped (EP) VECSELs, an average output power of 900 mW has been demonstrated from the undisclosed proprietary novalux extended cavity surface emitting laser (NECSEL) design. In contrast, modelocked NECSELs have only been demonstrated at 40mW. Recently, we presented a numerical study of EP-VECSELs suitable for modelocked operation; here, we demonstrate the first realization of this design. Power scaling is achieved with a lateral mode size increase. The competing electrical and optical requirements are, on the electrical side, low ohmic resistance, and on the optical side, low optical losses and low dispersion. Additionally, the device needs to operate in a fundamental mode for stable modelocking. We have fabricated and characterized 60 EP-VECSELs with varying dimensions and compared their lasing performance with our numerical simulations. The tradeoff between good beam quality and output power is discussed with an outlook to the modelocking of these EP-VECSELs. Initial EP-VECSEL devices have generated > 100 mW of cw output power. © 2006 IEEE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Modelocked lasers; optoelectronic devices; semiconductor lasers; vertical emitting lasers

Electroluminescence from a quantum-well LED using NEGF - Steiger, Sebastian; Veprek, Ratko G.; Witzigmann, Bernd (Proceedings - 2009 13th International Workshop on Computational Electronics, IWCE 2009, 2009)
Nonequilibrium Green's Functions (NEGF) are employed to model carrier transport and luminescence in a single-quantum-well light-emitting diode (LED). The sound theoretical formalism allows for a consistent description of coherence loss as well as fundamental scattering mechanisms and reveals details about physical phenomena such as the quantum-confined Stark and Franz-Keldysh effects, tunneling and carrier capture. A comparison to semiclassical results is made and similarities as well as differences are highlighted. ©2009 IEEE.
CRIS-Team Scopus Importer:2021-06-11

Electroluminescence in nanostructures of different dimensionalities: A comparative simulation study - Steiger, Sebastian; Veprek, Ratko G.; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2009)
We employ our simulation framework TDKP/AQUA to investigate bulk, planar quantum-well and V-groove quantum-wire light-emitting diodes. Carrier transport and spontaneous light emission are calculated selfconsistently for all degrees of quantization. The simulation is based on a semi-coherent picture of drift and diffusion along unquantized directions whereas confinement and luminescence are calculated from a multiband Schrödinger equation in the confined directions. The three structures with different quantization degrees are compared with respect to light conversion efficiency and overall output power. It is shown that carrier confinement greatly improves the radiative conversion efficiency but at the same time limits output power and enhances carrier leakage into the minority regions due to a reduced density of states. © 2009 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Luminescence; Nanostructures; Optoelectronics; Quantum-wells; Quantum-wires; Transport

Electromagnetic analysis of polarization and frequency selective tunable optical MEMS - Akcakoca, Ugur; Marklein, René; Witzigmann, Bernd; Hillmer, Hartmut (10th International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD 2010, 2010)
In this work, we present the computation of different integrated optical micro-electro-mechanical systems by applying the finite element method to the electromagnetic vectorial Helmholtz equation. The finite element solver combines state-of-the-art features with sophisticated symmetry handling and the perfectly matched layer approach to simulate open boundaries. The focus of investigation is on a photonic crystal slab for the purpose of a polarization selective filter in an integrated optical sensor system. The transmission characteristics of the filter is modeled with a finite element solver and the results are compared to analytic computations, published results, and the transfer matrix method for selected designs. A final design is found for maximum polarization selectivity at a given operation wavelength. ©2010 IEEE.
CRIS-Team Scopus Importer:2021-06-11

Electromagnetic study of magneto-optic surface plasmon resonance effects for biosensing applications - Jamali, Abdul Aleem; Kuebler, Sebastian; Mueglich, Nicolas; Witzigmann, Bernd; Ehresmann, Arno (Proceedings of SPIE - The International Society for Optical Engineering, 2013)
Biosensors are gaining interest in scientific research because of their wide variety of applications. Surface plasmon resonance (SPR) based biosensors are the most common platform for label-free biomolecular interaction analysis. In this paper, we present simulations of a magneto-optic SPR (MOSPR) biosensor by using a three-dimensional finite integration technique (FIT). In the past SPR based biosensors have been modeled with the FIT, here, we extend this technique by incorporating the anisotropic material Co for a MOSPR sensor. The MOSPR biosensor uses the properties of surface plasmon polaritons (SPPs) and transverse magneto-optic Kerr effect (TMOKE) simultaneously in the presence of an external magnetic field. We study the magneto-optical activity on the Au/Co/Au trilayer structures with opposite magnetization. The magneto-optic activity strongly depends on the metallic layer thicknesses and the refractive index of the dielectric. The simulation exhibits the electric and magnetic field distributions along the trilayer system. Based on the FIT simulations, we investigate the sensitivity of a MOSPR biosensor by changing the refractive index of the adjacent dielectric material from 1.33 to 1.40. Furthermore, we compare the performance of a MOSPR sensor to a SPR one. Finally experimental and simulation results of a MOSPR sensor in Kretschmann configuration are compared, verifying the used approach. © 2013 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Biosensors; Finite integration technique (FIT); Magneto-optic SPR (MOSPR); Surface plasmon resonance (SPR)

Electro-optical modeling of InP nanowire solar cells: Core-shell vs. axial structure - Yu, Shuqing; Kupec, Jan; Witzigmann, Bernd (10th International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD 2010, 2010)
We present an investigation of the photovoltaic effect in InP nanowire arrays for both axial and core-shell structures. A microscopic electro-optical model is used to analyze the currentvoltage relationships and cell efficiencies. It is found that coreshell structures provide a larger photocurrent and efficiency yet lower open circuit voltage than an axial structure. The analysis of the p-n junction operation explains this difference and gives design guidelines for nano-photovoltaic devices. ©2010 IEEE.
CRIS-Team Scopus Importer:2021-06-11

Electro-Optical Performance of Surface-Emitting Micromirror Superluminescent Diodes - Jentzsch, Bruno; Gomez-Iglesias, Alvaro; Tonkikh, Alexander; Niebling, Tobias; Witzigmann, Bernd (Physica Status Solidi-Rapid Research Letters, 2019)
Output power characteristics and efficiency of novel surface-emitting superluminescent diodes are presented. Tilted micromirrors terminate an in-plane waveguide, and laterally gain-guided modes are deflected perpendicularly to the anti-reflection-coated chip surface. The epitaxial structures are grown by a metal-organic vapor-phase epitaxy with several InGaAs/GaAs quantum wells emitting at a peak wavelength of 950 nm, and the chip technology involves only wafer-scale processes. The spectral full width at half maximum of the amplified spontaneous emission is larger than 10 nm. In a pulsed operation, a room temperature output power that exceeds 250 mW with a wall-plug efficiency higher than 15% is achieved.
CRIS-Team Scopus Importer:2021-06-11
Keywords: micromirrors; superluminescent diodes; surface emission; thin-film technology

Enhanced LWIR response of InP/InAsP quantum discs-in-nanowire array photodetectors by photogating and ultra-thin ITO contacts - Jeddi, Hossein; Adham, Kristi; Zhao, Yue; Witzigmann, Bernd; Römer, Friedhard; Bermeo, Marie; Borgström, Magnus T.; Pettersson, Håkan (Nanotechnology, 2024)
Here we report on an experimental and theoretical investigation of the long-wavelength infrared (LWIR) photoresponse of photodetectors based on arrays of three million InP nanowires with axially embedded InAsP quantum discs. An ultra-thin top indium tin oxide contact combined with a novel photogating mechanism facilitates an improved LWIR normal incidence sensitivity in contrast to traditional planar quantum well photodetectors. The electronic structure of the quantum discs, including strain and defect-induced photogating effects, and optical transition matrix elements were calculated by an 8-band k·p simulation along with solving drift-diffusion equations to unravel the physics behind the generation of narrow linewidth intersubband signals observed from the quantum discs.
CRIS-Team Scopus Importer:2024-07-19
Keywords: infrared photodetectors; long-wavelength infrared (LWIR); nanowire array photodetectors; nanowires; photogating; quantum discs-in-nanowires; ultra-thin ITO contacts

Extended micromagnetic model for the detection of superparamagnetic labels using a GMR vortex sensor - Wetterau, Lukas; Abert, Claas; Suess, Dieter; Albrecht, Manfred; Witzigmann, Bernd (Journal of Physics Communications, 2021)
A self-consistent micromagnetic model is proposed for simulating interactions between a superparamagnetic label particle and a low-noise GMR vortex sensor, focusing on most common operations such as label detection and saturation. For this purpose, we evaluate the combined action of vortex stray field and the applied external field. By solving the Landau-Lifshitz-Gilbert equation we find that a superparamagnetic label with a diameter of 60 nm can be successfully detected by a magnetic vortex structure assisted with an external magnetic field of 100 mT. Subsequently, the self-consistent spin diffusion model is applied to calculate electric response of a standard low-noise GMR vortex sensor to the presence of magnetically-saturated label. It is shown that the stray field of the activated label produces a detectable potential difference in the GMR sensor of 27.1 to 27.8 mV, the magnitude of which depends on location of the label with respect to the sensor surface.
CRIS-Team WoS Importer:2021-08-13

Frequency domain analysis of guided resonances and polarization selectivity in photonic crystal membranes - Kupec, Jan; Akcakoca, Ugur; Witzigmann, Bernd (Journal of the Optical Society of America B-Optical Physics, 2011)
Microstructured photonic crystal membranes are of great interest as compact filters in a variety of fields, including telecommunication and sensing. Here we present an analysis of the transmission and resonance behavior of a dielectricmembrane featuringperiodically arrangedholesusing the frequencydomain finite element analysis.We solveboth the source aswell as eigenvalue problemfor a given geometry. Applying symmetry considerations,we discardmodes that cannot be excited by incident transverse electro-magnetic (TEM) light simultaneously.We relate the results of the source problemto the modal analysis and obtain strong correspondence in both frequency and resonance quality factor. We find that the sharp resonances can be related to the eigenmodes of a rectangular dielectric resonator formed by the membrane and the holes of the photonic crystal. Analyzing noncircular holes for polarization-dependent transmittivity, the modal analysis presented herein constitutes a powerful tool to understand and identify occurrence of pronounced wideband polarization selectivity. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-11

Frequency domain analysis of modes in a photonic crystal micro-opto-electro-mechanical system with periodically arranged circular holes - Akcakoca, Ugur; Witzigmann, Bernd; Zamora, Ricardo; Kusserow, Thomas; Hillmer, Hartmut (Optical and Quantum Electronics, 2012)
In the present work we investigate the electromagnetic properties of a photonic crystalmicro-opto-electro-mechanical system. It consists of vertically arranged semiconductor membranes with air gaps forming a Fabry-Pérot cavity with distributed Bragg reflectors on each side. In the top membrane, circular holes are etched introducing a photonic crystal. We investigate the optical transmission behavior of this system by detailed simulation. It includes an analysis of the three-dimensional eigenmodes and calculation of the transmittivity from the source problem.We find that in addition to the vertical Fabry-Pérot cavity modes additional modes exist. The origin of these modes can be traced to resonances occurring in the top photonic crystal membrane. It is shown that the photonic crystal modes have a strong impact on the transmittivity of the filter system. © Springer Science+Business Media, LLC. 2011.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Fabry-pérot cavity; Modes; Photonic crystal membrane; Photonic crystal micro-opto-electro-mechanical system

Full-band Monte Carlo simulation of high-energy carrier transport in single photon avalanche diodes: Computation of breakdown probability, time to avalanche breakdown, and jitter - Dolgos, Denis; Meier, Hektor; Schenk, Andreas; Witzigmann, Bernd (Journal of Applied Physics, 2011)
The high-energy charge transport of electrons and holes in GaAs single photon avalanche diodes with multiplication region widths of 55 nm to 500 nm is investigated by means of the full-band Monte Carlo technique incorporating computationally efficient full-band phonon scattering rates. Compared to previous works, the solution of the Boltzmann transport equation and the incorporation of the full-band structure put the evaluation of the breakdown probability, the time to avalanche breakdown, and the jitter on deeper theoretical grounds. As a main result, the breakdown probability exhibits a steeper rise versus reverse bias for smaller multiplicator sizes. The time to avalanche breakdown and jitter decrease for smaller multiplicator widths. © 2011 American Institute of Physics.
CRIS-Team Scopus Importer:2021-06-11

Full-band Monte Carlo simulation of high-energy carrier transport in single photon avalanche diodes with multiplication layers made of InP, InAlAs, and GaAs - Dolgos, Denis; Meier, Hektor; Schenk, Andreas; Witzigmann, Bernd (Journal of Applied Physics, 2012)
We investigate the high-energy charge dynamics of electrons and holes in the multiplication process of single photon avalanche diodes. The technologically important multiplication layer materials InP and In 0.52Al 0.48As, used in near infrared photon detectors, are analyzed and compared with GaAs. We use the full-band Monte Carlo technique to solve the Boltzmann transport equation which improves the state-of-the-art treatment of high-field carrier transport in the multiplication process. As a result of the computationally efficient treatment of the scattering rates and the parallel central processing unit power of modern computer clusters, the full-band Monte Carlo calculation of the breakdown characteristics has become feasible. The breakdown probability features a steeper rise versus the reverse bias for smaller multiplication layer widths for InP, In 0.52Al 0.48As, and GaAs. Both the time to avalanche breakdown and jitter decrease with shrinking size of the multiplication region for the three examined III-V semiconductors. © 2012 American Institute of Physics.
CRIS-Team Scopus Importer:2021-06-11

Full-band Monte Carlo simulation of single photon avalanche diodes - Dolgos, Denis; Meier, Hektor; Schenk, Andreas; Witzigmann, Bernd (2013 IEEE Photonics Conference, IPC 2013, 2013)
Single photon avalanche diodes (SPADs) enable a variety of innovative applications in the fields of biology, medicine, and physics. The propagation of single photons with optical fibers requires the usage of telecommunication wavelengths in the near infrared (NIR) spectral range. NIR SPADs, which can be employed for this application, consist of an absorber layer (In 0.53Ga0.47As) and a multiplication layer (InP or In 0.52Al0.48As). The product of the quantum efficiency ηq, the probability that the photoexcited carrier survives into the multiplier Pc, and the breakdown probability Pb that the carrier activates a self-sustaining avalanche designate the photon detection efficiency [1] PDE = ηqPcPb. The breakdown probability contributes primarily to the electric field dependence of the PDE and increases with the electric field. Therefore, a higher electric field enhances the photon detection efficiency. However, band-to-band or trap-assisted tunneling in the multiplication layer initiate dark counts and degrade the performance of SPAD devices at higher electric fields. Hence, to obtain a higher photon detection efficiency for a given increase of the electric field and tunneling rate, a steep rise of the breakdown probability with applied bias is favorable. The SPAD's timing jitter arises from various sources. The avalanche build-up time is the main contribution to the timing jitter [1]. © 2013 IEEE.
CRIS-Team Scopus Importer:2021-06-11

Gain and bandwidth of InP nanowire array photodetectors with embedded photogated InAsP quantum discs - Jeddi, Hossein; Karimi, Mohammad; Witzigmann, Bernd; Zeng, Xulu; Hrachowina, Lukas; Borgstrom, Magnus T.; Pettersson, Hakan (Nanoscale, 2021)
Here we report on the experimental results and advanced self-consistent real device simulations revealing a fundamental insight into the non-linear optical response of n+-i-n+ InP nanowire array photoconductors to selective 980 nm excitation of 20 axially embedded InAsP quantum discs in each nanowire. The optical characteristics are interpreted in terms of a photogating mechanism that results from an electrostatic feedback from trapped charge on the electronic band structure of the nanowires, similar to the gate action in a field-effect transistor. From detailed analyses of the complex charge carrier dynamics in dark and under illumination was concluded that electrons are trapped in two acceptor states, located at 140 and 190 meV below the conduction band edge, at the interface between the nanowires and a radial insulating SiOx cap layer. The non-linear optical response was investigated at length by photocurrent measurements recorded over a wide power range. From these measurements were extracted responsivities of 250 A W-1 (gain 320)@20 nW and 0.20 A W-1 (gain 0.2)@20 mW with a detector bias of 3.5 V, in excellent agreement with the proposed two-trap model. Finally, a small signal optical AC analysis was made both experimentally and theoretically to investigate the influence of the interface traps on the detector bandwidth. While the traps limit the cut-off frequency to around 10 kHz, the maximum operating frequency of the detectors stretches into the MHz region.
CRIS-Team Scopus Importer:2021-06-11

Gain Characteristics of Optically Pumped UVC Lasers with Wide AlGaN Single-Quantum-Well Active Regions - Cardinali, Giulia; Kölle, Sebastian; Schulz, Alexander; Susilo, Norman; Hauer Vidal, Daniel; Guttmann, Martin; Blonski, Markus A.; Römer, Friedhard; Witzigmann, Bernd; Nippert, Felix; Wagner, Markus R.; Wernicke, Tim; et al. (physica status solidi (a), 2024)
Herein, the lasing threshold and gain characteristics of ultraviolet-C optically pumped edge-emitting lasers with thick single-quantum-well (SQW) active regions are investigated by the variable-stripe length method. Positive net modal gain is observed in lasers with AlGaN-based SQWs with thicknesses up to 12 nm. The lasers show a reduction of the threshold power density with increasing SQW thickness, with the lowest threshold of 1.3 MW cm−2 achieved for a 9 nm SQW laser. The high gain and low threshold in lasers with thick quantum wells are attributed to lasing from excited states, where the polarization fields are screened by the carriers in the fundamental state and the barriers, thus recovering larger electron and hole wavefunctions overlap. These findings are supported by k · p simulations, and for a 9 nm SQW, the calculation predicts a contribution of the fundamental transition to the gain of 75% for non-resonant optical excitation and below 1% for resonant optical or electrical excitation.
CRIS-Team Scopus Importer:2024-03-29
Keywords: AlGaN; numerical simulations; optical gain; semiconductor lasers

GaN-based nanocolumn LEDs: Impact of strain engineering on the electro-optical performance - Veprek, Ratko G.; Steiger, Sebastian; Witzigmann, Bernd (Physica Status Solidi (C) Current Topics in Solid State Physics, 2009)
A computation of the electronic properties of GaN nanocolumn LEDs with optically active InGaN quantum disks is presented. Using the simulation framework AQUA/tdkp, the relaxation of intrinsic strains in the selected 3D structure and its effects on the built-in piezoelectric potential and strain dependent bandedge shifts are computed. The results show a strong relaxation of the compressive strains in the InGaN quantum disk compared to usual broad area grown structures suggesting that lower wavelength emission can be achieved at considerable lower indium contents. © 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2021-06-11

GaN nanowire arrays with nonpolar sidewalls for vertically integrated field-effect transistors - Yu, Feng; Yao, Shengbo; Roemer, Friedhard; Witzigmann, Bernd; Schimpke, Tilman; Strassburg, Martin; Bakin, Andrey; Schumacher, Hans Werner; Peiner, Erwin; Wasisto, Hutomo Suryo; Waag, Andreas (Nanotechnology, 2017)
Vertically aligned gallium nitride (GaN) nanowire (NW) arrays have attracted a lot of attention because of their potential for novel devices in the fields of optoelectronics and nanoelectronics. In this work, GaN NW arrays have been designed and fabricated by combining suitable nanomachining processes including dry and wet etching. After inductively coupled plasma dry reactive ion etching, the GaN NWs are subsequently treated in wet chemical etching using AZ400K developer (i.e., with an activation energy of 0.69 ±0.02 eV and a Cr mask) to form hexagonal and smooth a-plane sidewalls. Etching experiments using potassium hydroxide (KOH) water solution reveal that the sidewall orientation preference depends on etchant concentration. A model concerning surface bonding configuration on crystallography facets has been proposed to understand the anisotropic wet etching mechanism. Finally, NW array-based vertical field-effect transistors with wrap-gated structure have been fabricated. A device composed of 99 NWs exhibits enhancement mode operation with a threshold voltage of 1.5 V, a superior electrostatic control, and a high current output of >10 mA, which prevail potential applications in next-generation power switches and high-temperature digital circuits.
CRIS-Team Scopus Importer:2021-06-11
Keywords: GaN nanowire array; nonpolar plane; vertical field effect transistors; wet etching

Germanium Plasmon Enhanced Resonators for Label-Free Terahertz Protein Sensing - Bettenhausen, Maximilian; Roemer, Friedhard; Witzigmann, Bernd; Flesch, Julia; Kurre, Rainer; Korneev, Sergej; Piehler, Jacob; You, Changjiang; Kazmierczak, Marcin; Guha, Subhajit; Capellini, Giovanni; Schroeder, Thomas (Frequenz, 2018)
A Terahertz protein sensing concept based on subwavelength Ge resonators is presented. Ge bowtie resonators, compatible with CMOS fabrication technology, have been designed and characterized with a resonance frequency of 0.5 THz and calculated local intensity enhancement of 10.000. Selective biofunctionalization of Ge resonators on Si wafer was achieved in one step using lipoic acid-HaloTag ligand (LA-HTL) for biofunctionalization and passivation. The results lay the foundation for future investigation of protein tertiary structure and the dynamics of protein hydration shell in response to protein conformation changes.
CRIS-Team Scopus Importer:2021-06-11
Keywords: protein conformation; semiconductor plasmonics; terahertz sensor

Ge(Sn) nano-island/Si heterostructure photodetectors with plasmonic antennas - Schlykow, Viktoria; Manganelli, Costanza Lucia; Roemer, Friedhard; Clausen, Caterina; Auge, Lion; Schulze, Jörg; Katzer, Jens; Schubert, Michael Andreas; Witzigmann, Bernd; Schroeder, Thomas; Capellini, Giovanni; Fischer, Inga Anita; et al. (Nanotechnology, 2020)
We report on photodetection in deep subwavelength Ge(Sn) nano-islands on Si nano-pillar substrates, in which self-aligned nano-antennas in the Al contact metal are used to enhance light absorption by means of local surface plasmon resonances. The impact of parameters such as substrate doping and device geometry on the measured responsivities are investigated and our experimental results are supported by simulations of the three-dimensional distribution of the electromagnetic fields. Comparatively high optical responsivities of about 0.1 A W-1 are observed as a consequence of the excitation of localized surface plasmons, making our nano-island photodetectors interesting for applications in which size reduction is essential.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Ge; GeSn; localized surface plasmon resonances; nanoheteroepitaxy; photodetector

Green to blue polarization compensated c-axis oriented multi-quantum wells by AlGaInN barrier layers - Dadgar, Armin; Groh, L.; Metzner, S.; Neugebauer, S.; Blaesing, J.; Hempel, T.; Bertram, Frank; Christen, Juergen; Krost, A.; Andreev, Z.; Witzigmann, Bernd (Applied Physics Letters, 2013)
We report on an over 50% reduction in polarization field strength in c-axis oriented InGaN multi-quantum wells (MQW) by applying quaternary AlGaInN barrier layers with better polarization matching to InGaN than GaN barriers. With the reduction in polarization fields, a strong blue-shift in photoluminescence is observed in agreement with theoretical expectation and simulations. By gracing incidence x-ray diffraction measurements, we demonstrate that partial relaxation already occurs for GaN/InGaN MQWs. As a consequence, the requirement of higher In-content layers for green light emission is in conflict with increasing strain leading to lattice relaxation. © 2013 American Institute of Physics.
CRIS-Team Scopus Importer:2021-06-11

High Responsivity of InP/InAsP Nanowire Array Broadband Photodetectors Enhanced by Optical Gating - Karimi, Mohammad; Zeng, Xulu; Witzigmann, Bernd; Samuelson, Lars; Borgstrom, Magnus T.; Pettersson, Hakan (Nano Letters, 2019)
High-performance photodetectors operating in the near-infrared (0.75-1.4 μm) and short-wave infrared (1.4-3.0 μm) portion of the electromagnetic spectrum are key components in many optical systems. Here, we report on a combined experimental and theoretical study of square millimeter array infrared photodetectors comprising 3 million n+-i-n+ InP nanowires grown by MOVPE from periodically ordered Au seed particles. The nominal i-segment, comprising 20 InAs0.40P0.60 quantum discs, was grown by use of an optimized Zn doping to compensate the nonintentional n-doping. The photodetectors exhibit bias- and power-dependent responsivities reaching record-high values of 250 A/W at 980 nm/20 nW and 990 A/W at 532 nm/60 nW, both at 3.5 V bias. Moreover, due to the embedded quantum discs, the photoresponse covers a broad spectral range from about 0.70 to 2.5 eV, in effect outperforming conventional single InGaAs detectors and dual Si/Ge detectors. The high responsivity, and related gain, results from a novel proposed photogating mechanism, induced by the complex charge carrier dynamics involving optical excitation and recombination in the quantum discs and interface traps, which reduces the electron transport barrier between the highly doped n+ contact and the i-segment. The experimental results obtained are in perfect agreement with the proposed theoretical model and represent a significant step forward toward understanding gain in nanoscale photodetectors and realization of commercially viable broadband photon detectors with ultrahigh gain.
CRIS-Team Scopus Importer:2021-06-11
Keywords: discs-in-nanowires; infrared photodetectors; interface traps; nanowire array photodetectors; Nanowires; optical gain; photogating; quantum discs

Impact ionization scattering model based on the random-k approximation for GaAs, InP, InAlAs, and InGaAs - Dolgos, Denis; Schenk, Andreas; Witzigmann, Bernd (Journal of Applied Physics, 2012)
The inclusion of momentum conservation and the evaluation of the double Coulomb transition matrix elements render the calculation of the impact ionization scattering rates with first principle approaches computationally expensive and their numerical implementation laborious. Despite the positive assessment of Kane's random-k approximation, the impact ionization rates and the secondary carrier energies for the III-V semiconductors GaAs, InP, In 0.52Al 0.48As, and In 0.53Ga 0.47As have not been provided to the charge transport modeling community in terms of analytical fit functions yet. We provide the impact ionization scattering rates as modified Keldysh formulas and the secondary carrier energies as straight line fits. The band structure computation is based on the empirical pseudopotential method. © 2012 American Institute of Physics.
CRIS-Team Scopus Importer:2021-06-11

Impedance Matching of THz Plasmonic Antennas - Bettenhausen, Maximilian; Gruessing, Soenke; Hardt, Elena; Flesch, Julia; Roemer, Friedhard; Chavarin, Carlos Alvarado; Klesse, Wolfgang M.; You, Changjiang; Piehler, Jacob; Capellini, Giovanni; Witzigmann, Bernd (Journal of Infrared, Millimeter, and Terahertz Waves, 2019)
Plasmonic antennas with subwavelength gaps work as sensing devices for molecules for the optical and terahertz (THz) frequency range. In such a configuration, the sensing gap creates a high impedance, in contrast to the antenna itself, which is designed for low ohmic losses. Besides metals, highly doped semiconductors can be used as plasmonic materials for the THz range, which increase the impedance of the antenna while keeping the strong electromagnetic intensity enhancement in the sensing gap. Still, a substantial impedance mismatch remains. In this paper, an approach for matching the gap to the antenna impedance is proposed. First, a germanium semiconductor slab antenna is designed for THz operation, with a dipole resonance at 4 THz. Based on an impedance analysis, an impedance matching element consisting of a graphene sheet is inserted in parallel to the gap. Employing impedance matching, a strong intensity enhancement occurs and the normal dipole mode of the plasmonic antenna is split into a symmetric one at 0.67 THz and an antisymmetric one at 4 THz. The symmetric mode provides a very high-quality factor and a substantial enhancement; furthermore, its resonance can be tuned by the Fermi level adjustment in the graphene. First designs of this structure are computed analytically with a circuit model and are verified by 3D full-wave simulations.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Germanium on silicon; Graphene; Impedance matching; Plasmonics; Semiconductor antennas

InGaN nanorod LEDs: A performance assessment - Witzigmann, Bernd; Deppner, Marcus; Romer, Friedhard (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2012)
Light Emitting Diodes (LEDs) have become an attractive concept as efficient light sources. In this contribution, the electro-optical performance of Ill-nitride based core-shell nanorod LEDs is investigated by detailed simulation. In contrast to their planar counterparts, they possess increased active region area on small footprint, non-polar active regions with c-plane vertical growth, and form horizontal two-dimensional active photonic crystals for the optical extraction process. © 2012 IEEE.
CRIS-Team Scopus Importer:2021-06-11

Inhomogeneous spectral broadening in deep ultraviolet light emitting diodes - Roemer, Friedhard; Witzigmann, Bernd; Guttmann, Martin; Susilo, Norman; Wernicke, Tim; Kneissl, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
We investigate the spectral broadening in deep ultraviolet (UV) multi quantum well light emitting diodes (LED) by modeling the emission spectra. Experimental emission spectra of deep UV LEDs exhibit a at tail towards lower energies and a steep decrease towards high energies that cannot be explained by convolution of the spectrum with a broadening function. We devise a luminescence model based on the broadening of the density of states (DOS) function which is consistent with the experimental spectra. The broadening of the DOS also explains the emission red shift with respect to the quantum well subband transitions. In addition, we investigate the in uence of the DOS broadening on the carrier and luminescence in the active region.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Bimolecular recombination; III-nitride; Inhomogeneous broadening; Light emitting diode; UVC

InP-based narrow-linewidth widely tunable quantum dot distributed feedback lasers InP-basierte weit verstimmbare Quantenpunkt-Laser mit verteilten Rückkopplungsgittern und schmalen Emissionslinienbreiten - Becker, A; Bjelica, M.; Sichkovskyi, V.; Eyal, O.; Rippien, A.; Schnabel, F.; Baum, P.; Witzigmann, Bernd; Eisenstein, G.; Reithmaier, J.P. (16. ITG-Fachtagung Photonische Netze - 16th ITG Conference on Photonic Networks, 2020)

InP-basierte weit verstimmbare Quantenpunkt-Laser mit verteilten Rückkopplungsgittern und schmalen Emissionslinienbreiten - Becker, Annette; Bjelica, Marko; Sichkovskyi, Vitalii; Eyal, Ori; Rippien, Anna; Schnabel, Florian; Baum, Philipp; Witzigmann, Bernd; Eisenstein, Gadi; Reithmaier, Johann Peter (Photonische Netze - 16. ITG-Fachtagung, 2020)
For high-capacity coherent optical communication narrow linewidth widely tunable distributed feedback (DFB) lasers as reference lasers are needed. InP-based quantum dot (QD) material developed for 1.55 µm enables tailoring of device properties, like gain, bandwidth and low linewidth enhancement factor (α-factor) that are favorable for such an application. Theoretical considerations taking into account the quasi zero-dimensional nature of the active zone, clearly predict a strong reduction of the laser linewidth by appropriate tailoring of the QD material design. QD lasers with 2 and 5 QD layers were grown by molecular beam epitaxy (MBE). Distributed feedback (DFB) lasers were fabricated with integrated micro-heaters in form of meandric resistors. Especially developed etch stop layers provide accurate shaping of the laser ridges. The lasers are coupled in pairs by integrated 3dB-couplers to enable the realization of widely tunable laser arrays with a tuning range of 50 nm covering the C+ band. The purpose of these arrays is to provide compact, flexibly applicable and tunable laser sources for coherent detection. The linewidth measurements for the investigated devices are in good accordance to simulated values. This allows a targeted modification of the epitaxy and QD design in the future. With DFB lasers consisting of 5 QD layers a continuous single-mode thermal tuning range of up-to 10 nm per laser and a linewidth considerably below 1 MHz could be obtained. A comparison of the two designs confirms the theoretically predicted reduction of linewidth for the high-gain design with 5 QD layers, which clearly confirmed the first time directly the relationship of a low α-factor, as been realized by QD material, and the strongly reduced emission linewidth independent on other structural parameters.
CRIS-Team Scopus Importer:2021-06-11

InP nanowire array solar cells achieving 13.8% efficiency by exceeding the ray optics limit - Wallentin, Jesper; Anttu, Nicklas; Asoli, Damir; Huffman, Maria; Aberg, Ingvar; Magnusson, Martin H.; Siefer, Gerald; Fuss-Kailuweit, Peter; Dimroth, Frank; Witzigmann, Bernd; Xu, H. Q.; Samuelson, Lars; et al. (Science, 2013)
Photovoltaics based on nanowire arrays could reduce cost and materials consumption compared with planar devices but have exhibited low efficiency of light absorption and carrier collection. We fabricated a variety of millimeter-sized arrays of p-type/intrinsic/n-type (p-i-n) doped InP nanowires and found that the nanowire diameter and the length of the top n-segment were critical for cell performance. Efficiencies up to 13.8% (comparable to the record planar InP cell) were achieved by using resonant light trapping in 180-nanometer-diameter nanowires that only covered 12% of the surface. The share of sunlight converted into photocurrent (71%) was six times the limit in a simple ray optics description. Furthermore, the highest open-circuit voltage of 0.906 volt exceeds that of its planar counterpart, despite about 30 times higher surface-to-volume ratio of the nanowire cell.
CRIS-Team Scopus Importer:2021-06-11

Integration of wet-etched GaN nanowires for vertical power transistors - Yu, Feng; Yao, Shengbo; Römer, Friedhard; Witzigmann, Bernd; Wasisto, Hutomo Suryo; Waag, Andreas (Mikro-Nano-Integration - 6. GMM-Workshops, 2016)
A top-down fabrication approach of GaN vertical transistors through integrating vertically aligned nanowires (NWs) has been reported here. By employing wet chemical etching, NWs with smooth a-plane sidewalls as well as special mushroom-like geometry are realized. The diameter of NWs can be controlled to be as small as 50 nm and their aspect ratio can reach up to 60. A fabricated transistor, integrating 99 NWs, exhibits enhancement-mode (E-mode) operation with a threshold voltage of 1.5 V, a high on and off current ratio of 109, a small subthreshold swing of 67 mV/Dec, and a high drain current (Id) output of Id > 10 mA, indicating that such vertical GaN devices are promising for future candidate in power electronics.
CRIS-Team Scopus Importer:2021-06-11

Introduction to the issue on numerical simulation of optoelectronic devices - Piprek, Joachim; Witzigmann, Bernd; Park, Seoung-Hwan; Bellotti, Enrico (IEEE Journal of Selected Topics in Quantum Electronics, 2013)
CRIS-Team Scopus Importer:2021-06-11

Investigation of relative intensity noise in asymmetric external cavity semiconductor laser sensors: Influence of dual-line spectral separation and linewidth enhancement factor - Shrestha, Jyoti C.; Blom, Sven; Witzigmann, Bernd; Hillmer, Hartmut H. (IEEE Sensors Journal, 2015)
A tunable gas sensor based on an asymmetric external cavity semiconductor lasers oscillating on two spectral lines is presented and investigated experimentally and theoretically. In order to minimize the cost and size of the gas sensor, relative intensity noise (RIN) as a detection methodology is used to measure the intensity levels and intensity differences of two lines. The influence of the spectral separation of the two lines on the RIN has been investigated and explained in the framework of the interplay of the linewidth enhancement factor and two different cavity lengths of the two lines. Each line is related to a different cavity length, which we denote as an asymmetric laser. It has been found that for larger line spacing, the sensor reveals a higher sensitivity to intensity variations of the lines than for smaller line spacing. The experiments show the largest change of RIN at an intensity difference between the two lines of -5 and +5 dB. Very interesting is the experimental result that each line can be tuned in a stable single line condition. For a line intensity ratio between -40 and -15 dB as well as around +20 dB, two ranges of constant RIN have been found, which are different in the averaged RIN by ≈ 6 up to 10 dB depending on the line separation. The difference of ≈6 up to 10 dB can be quantitatively explained by the asymmetric cavity design and linewidth enhancement factor.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Asymmetric laser cavity; line spacing; relative intensity noise (RIN); semiconductor lasers; sensors

Large linewidth reduction in semiconductor lasers based on atom-like gain material - Septon, Tali; Becker, Annette; Gosh, Sutapa; Shtendel, Gal; Sichkovskyi, Vitalii; Schnabel, Florian; Sengill, Anna; Elica, Marko Bj; Witzigmann, Bernd; Reithmaier, Johann Peter; Eisenstein, Gadi (Optica, 2019)
With a new generation of quantum dot (QD) optical gain material comprising atom-like features, the fundamental spectral characteristics of laser emission have been improved significantly. We describe the spectral and power characteristics of continuous wave (CW) single-mode InAs/AlGaInAs/InP QD distributed feedback lasers operating at 1.5 μm. Linewidths as narrow as 60 kHz (30 kHz ± 10 kHz intrinsic linewidth) at 20°C, which broadens to only 280 kHz (80 kHz ± 10 kHz intrinsic linewidth) at 80°C, have been achieved. The laser exhibits high output powers of 58 mW at 20°C and 26 mW at 80°C with side mode suppression ratios exceeding 50 dB. These record values stem from high uniformity of the QDs and a large dot density. The linewidth was measured by two techniques that confirm each other: delayed self-heterodyne interferometry and optical frequency comb interferometry. A model fits the experimental results well and enables extraction of the bias and temperature dependent α parameter. At 20°C, α is less than 0.5 at threshold and increases to only 0.9 at 150 mA above threshold. The corresponding values at 80°C are 2 and 2.5. These results imply a great potential of QD lasers for the most demanding applications in terms of spectral purity, such as coherent optical communication systems and optical metrology.
CRIS-Team Scopus Importer:2021-06-11

Light absorption and emission in nanowire array solar cells - Kupec, Jan; Stoop, Ralph L.; Witzigmann, Bernd (Optics Express, 2010)
Inorganic nanowires are under intense research for large scale solar power generation intended to ultimately contribute a substantial fraction to the overall power mix. Their unique feature is to allow different pathways for the light absorption and carrier transport. In this publication we investigate the properties of a nanowire array acting as a photonic device governed by wave-optical phenomena. We solve the Maxwell equations and calculate the light absorption efficiency for the AM1.5d spectrum and give recommendations on the design. Due to concentration of the incident sunlight at a microscopic level the absorptivity of nanowire solar cells can exceed the absorptivity of an equal amount of material used in thin-film devices. We compute the local density of photon states to assess the effect of emission enhancement, which influences the radiative lifetime of excess carriers. This allows us to compute the efficiency limit within the framework of detailed balance. The efficiency is highly sensitive with respect to the diameter and distance of the nanowires. Designs featuring nanowires below a certain diameter will intrinsically feature low short-circuit current that cannot be compensated even by increasing the nanowire density. Optimum efficiency is not achieved in densely packed arrays, in fact spacing the nanowires further apart (simultaneously decreasing the material use) can even improve efficiency in certain scenarios. We observe absorption enhancement reducing the material use. In terms of carrier generation per material use, nanowire devices can outperform thin-film devices by far. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-11

Local near field assisted ablation of fused silica: An experimental and theoretical study - Jamali, Abdul Aleem; Witzigmann, Bernd; Morarescu, Rodica; Baumert, Thomas; Traeger, Frank; Hubenthal, Frank (Applied Physics A: Materials Science and Processing, 2013)
In this contribution we present recent experimental and theoretical results on local near-field assisted laser ablation. Along these lines, we have generated sub-diffraction sized nanostructures on fused silica substrates, exploiting the local near fields of highly ordered triangular gold nanoparticle arrays generated by nanosphere lithography. After preparation, the nanoparticle arrays were irradiated with a single 35 fs long laser pulse with a central wavelength of λ = 790 nm. The pulse energy was set to E = 3.9 μJ, resulting in a fluence well below the ablation threshold of the fused silica substrates. In addition, 3D electromagnetic simulations using a finite integration technique in time domain have been performed. The simulations demonstrate that indeed the local field in the vicinity of the tips of the triangular nanoparticles overcome the ablation threshold and easily explain the generated nanostructures. Most importantly, the simulations show, that higher order modes contribute to the ablation process. These modes cause ablation along the side edges of the nanoparticles. Finally, we demonstrate, that the optical properties of the triangular nanoparticles, which can be tuned by their morphology, are crucial parameters for the generation of the ablation structures.
CRIS-Team Scopus Importer:2021-06-11

Luminescence and efficiency optimization of InGaN/GaN core-shell nanowire LEDs by numerical modelling - Roemer, Friedhard; Deppner, Marcus; Andreev, Zhelio; Koelper, Christopher; Sabathil, Matthias; Strassburg, Martin; Ledig, Johannes; Li, Shunfeng; Waag, Andreas; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2012)
We present a computational study on the anisotropic luminescence and the efficiency of a core-shell type nanowire LED based on GaN with InGaN active quantum wells. The physical simulator used for analyzing this device integrates a multidimensional drift-diffusion transport solver and a k · p Schrödinger problem solver for quantization effects and luminescence. The solution of both problems is coupled to achieve self-consistency. Using this solver we investigate the effect of dimensions, design of quantum wells, and current injection on the efficiency and luminescence of the core-shell nanowire LED. The anisotropy of the luminescence and re-absorption is analyzed with respect to the external efficiency of the LED. From the results we derive strategies for design optimization. © 2012 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Computational electronics; Core-shell; Gallium nitride; Kp-Method; Light emitting diode; Nano structure

Luminescence and Internal Quantum Efficiency of Deep UV Light Emitting Diodes - Romer, Friedhard; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2020)
Deep ultraviolet (DUV) light emitting diodes (LED) made of Aluminium Gallium Nitride (AlGaN) are increasingly considered as light sources for medical as well as material processing applications. Recent research on AlGaN DUV LEDs focuses on the enhancement of the efficiency. The efficiency of AlGaN LEDs is limited by a low hole injection efficiency and TM-polarized emission requiring a careful design. In this context we are demonstrating the physics based modelling of AlGaN DUV LEDs by means of a self consistent simulation approach. The simulation model is validated and calibrated comparing experiment and simulation. We demonstrate that electron leakage presents a major contribution to the internal loss and analyse the impact of the active region design.
CRIS-Team Scopus Importer:2021-06-11

Luminescence distribution in the multi-quantum well region of III-nitride light emitting diodes - Römer, Friedhard; Witzigmann, Bernd (Light-Emitting Diodes: Materials, Devices, and Applications for Solid State Lighting XXI 2017, 2017)
Keywords: ideality factor; carrier transport simulation; light emitting diode; III-nitride; multi quantum well

Micromagnetic simulations of submicron vortex structures for the detection of superparamagnetic labels - Wetterau, Lukas; Abert, Claas; Suess, Dieter; Albrecht, Manfred; Witzigmann, Bernd (Sensors, 2020)
We present a numerical investigation on the detection of superparamagnetic labels using a giant magnetoresistance (GMR) vortex structure. For this purpose, the Landau–Lifshitz–Gilbert equation was solved numerically applying an external z-field for the activation of the superparamagnetic label. Initially, the free layer’s magnetization change due to the stray field of the label is simulated. The electric response of the GMR sensor is calculated by applying a self-consistent spin-diffusion model to the precomputed magnetization configurations. It is shown that the soft-magnetic free layer reacts on the stray field of the label by shifting the magnetic vortex orthogonally to the shift direction of the label. As a consequence, the electric potential of the GMR sensor changes significantly for label shifts parallel or antiparallel to the pinning of the fixed layer. Depending on the label size and its distance to the sensor, the GMR sensor responds, changing the electric potential from 26.6 mV to 28.3 mV.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Giant magnetoresistance; Lab-on-a-chip device; Micromagnetic simulations; Superparamagnetic labels; Vortex structures

Modeling of plasmonic semiconductor THz antennas in square and hexagonal array arrangements - Gruessing, Soenke; Witzigmann, Bernd; Roemer, Friedhard; Capellini, Giovanni; Alvarado, Carlos; Klesse, Wolfgang M.; Hardt, Elena; Piehler, Jacob; You, Changjiang; Flesch, Julia (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
Here, we present 3D solutions of Maxwell's equations using the finite element method (FEM) for sub-wavelength plasmonic THz antennas in array configurations. We show that mutual coupling between neighboring antennas causes the arrays spectral response to change with different array densities and arrangements. The simulation results of the spectral response of the antennas are in very good agreement to the experiments. Finally, in order to investigate the sensing performance of the antennas, simulations with different feed gap materials were carried out.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Antenna; Bio-sensing; Field enhancement; Germanium; Plasmonic; Proteins; THz

Modelling surface effects in nano wire optoelectronic devices - Roemer, Friedhard; Witzigmann, Bernd (Journal of Computational Electronics, 2012)
Recent research on optoelectronic devices focuses on nano structuring which is expected to improve the performance and reduce the production costs of light emitting diodes for lighting purposes and solar cells, for instance. Structuring on the sub-micrometer scale increases the surface with respect to the active volume so that surface effects become crucial for the device performance. In this work we demonstrate the computational modelling of nano structured optoelectronic devices to complement the experiment. The implementation of the simulation model considers surface effects in these devices using a true area box method discretization. The derived surface models are applied on the self-consistent simulation of nano wire quantum disk light emitting diodes. By the computational study we demonstrate that the surface physical effects are critical for the performance of nano-structured optoelectronic devices and that surface recombination can lead to a low efficiency. © Springer Science+Business Media LLC 2012.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Box method; Light emitting diode; Nano structure; Optoelectronic device; Surface effects

Modifying the Complex Refractive Index of Thin-Films for Nanooptical Applications - Kunne, Marco; Kusserow, Thomas; Witzigmann, Bernd; Hillmer, Hartmut (2024 International Conference on Optical MEMS and Nanophotonics (OMN), 2024)
We present a method to generate 2D refractive index patterns in thin-films for nanooptical applications, like metasurfaces and plasmonics. The method is based on standard deposition, lithography and manipulation processes and can be applied to numerous material systems. Examples for modification of indium tin oxide and transition metal nitride layers are given.
CRIS-Team Scopus Importer:2025-02-04
Keywords: complex refractive index; ITO; material modification; nanooptics; TiN; ZrN

Nanowire arrays for photovoltaics and lighting: Electronic and optical properties - Witzigmann, Bernd; Deppner, M.; Yu, S.; Kupec, J.; Römer, F. (Integrated Photonics Research, Silicon and Nanophotonics, IPRSN 2012, 2012)
Semiconductor nanowire arrays possess both subwavelength electromagnetic as well asquantum electronic features. As active elements, they are attractive device concepts for optoelectronics. In this paper, the properties of nanowire arrays are discussed for their use as light emitting diodes and photovoltaic devices. © 2012 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-11

Nanowire solar cells: Electro-optical performance - Witzigmann, Bernd (Handbook of Optoelectronic Device Modeling and Simulation: Lasers, Modulators, Photodetectors, Solar Cells, and Numerical Methods, 2017)
Nanowire arrays show unique optical and electronic features for photovoltaic applications. It has been demonstrated that they exhibit intrinsic optical antireflection properties [1, 2]. Moreover, they also can act as optical microconcentrators [3] that focus light to an active region. Nanowires have a large aspect ratio, improving the electronic properties by combining a long optical absorption path along the wire axis and a short lateral carrier extraction [4]. Short carrier extraction paths are beneficial for the carrier collection efficiency. These mechanisms are illustrated in Figure 42.1. On the left, a conventional bulk solar cell collects light in the vertical direction, and the photogenerated carriers move to the respective contacts causing the photo current. A nanostructured solar cell (Figure 42.1a) can act as an optical concentrator in order to focus the incoming light to a small area. Moreover, the carrier extraction path length to the contacts is reduced, which minimizes the probability of carrier loss by unwanted recombination.
CRIS-Team Scopus Importer:2021-06-11

Narrow-linewidth 1.5 μm quantum dot distributed feedback lasers - Becker, Annette; Sichkovskyi, Vitalii; Bjelica, Marko; Eyal, Ori; Baum, Philipp; Rippien, Anna; Schnabel, Florian; Witzigmann, Bernd; Eisenstein, Gadi; Reithmaier, Johann Peter (Proceedings of SPIE - The International Society for Optical Engineering, 2016)
The ever-growing need for higher data rates is a driving force for the implementation of higher order coherent communication formats. A key element in coherent detection is the local oscillator (LO) of the decoding unit. This device has to provide coherent light with a narrow linewidth in order to distinguish between different phase and amplitude states of the incoming signal. As predicted by theory, a drastic linewidth reduction is expected from quantum dot (QD) laser materials by the quasi zero-dimensional nature of the gain function. The impact of different gain materials consisting of different numbers of QD layers on the linewidth of distributed feedback (DFB) lasers was investigated and shows an unambiguous dependence on the layer design. Intrinsic linewidths as low as 110 kHz could be determined.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Distributed feedback laser; Linewidth enhancement factor; Optical communication; Quantum dot laser

Narrow-linewidth 1.5 μm quantum dot distributed feedback lasers for next generation coherent communication - Becker, Annette; Septon, Tali; Ghosh, Sutapa; Bjelica, Marco; Sichkovskyi, Vitalii; Rippien, Anna; Schnabel, Florian; Witzigmann, Bernd; Eisenstein, Gadi; Reithmaier, Johann Peter (Photonische Netze - 19. ITG-Fachtagung, 2020)
InP-based quantum dot (QD) material with five QD layers in the active region was used to fabricate distributed feedback (DFB) lasers with a cavity length of -1.5 mm. QDs enable tailoring of device properties, like gain, bandwidth and low linewidth enhancement factor (α-factor) that are favourable for applications in next generation coherent communication [1]. Theoretical considerations taking into account the quasi zero-dimensional nature of the active material, clearly predict a strong reduction of the laser linewidth by appropriate dot design [2]. Previous results on QD DFB lasers using 2 QD layers in the active region exhibited a linewidth of 110 kHz [3]. New results based on 5 QD layers suggest considerably lower linewidth as was predicted by theory. First results suggest linewidths below 50 kHz.
CRIS-Team Scopus Importer:2021-06-11

NEGF quantum transport for green MQW nitride LEDs - Shedbalkar, Akshay; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2017)
This work presents a non-equilibrium Green's function (NEGF) based simulation of blue and green single and multi-quantum well light emitting diodes (LEDs). The simulations provide insight into transport phenomena like tunnelling, hot carrier and back-scattering and the behavior of the density of states above the active region. It is shown that the electron density in the quantum wells is largely in equilibrium in contrast to the quantum well barrier.
CRIS-Team Scopus Importer:2021-06-11

Non equilibrium Green’s function quantum transport for green multi-quantum well nitride light emitting diodes - Shedbalkar, Akshay; Witzigmann, Bernd (Optical and Quantum Electronics, 2018)
This work presents a non-equilibrium Green’s function (NEGF) based simulation of a green nitride multi-quantum well light emitting diode (LED). A carrier–carrier scattering model based on the Büttiker approach is implemented for LEDs, which has some challenges due to the bipolar nature of the device, large bandgap of nitride devices and non-equilibrium conditions. It is shown that the implemented model, which uses two sets of probe Fermi levels, represents the physics of carrier–carrier scattering in an LED. The simulations provide insight into transport phenomena like tunnelling, hot carriers, back-scattering and accurate DOS in quantized regions. In addition, it is shown that the electron density in the quantum wells is divided into bulk and quantized populations and that the bulk population in the quantum well region does not follow an analytical equilibrium quantum well model.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Büttiker probes; Green LED; NEGF; Two Fermi level method

Normally off Vertical 3-D GaN Nanowire MOSFETs with Inverted p-GaN Channel - Yu, Feng; Strempel, Klaas; Fatahilah, Muhammad Fahlesa; Zhou, Hao; Roemer, Friedhard; Bakin, Andrey; Witzigmann, Bernd; Schumacher, Hans Werner; Wasisto, Hutomo Suryo; Waag, Andreas (IEEE Transactions on Electron Devices, 2018)
This paper reports on the normally off GaN vertical MOSFETs based on nanowires (NWs) with an inverted p-GaN channel and a wrap-around-gate structure for the first time. Both inductively coupled plasma dry reactive-ion etching and wet-chemical etching were employed to fabricate the vertically aligned GaN NWs from epitaxial thin films with a specified doping profile. During the wet etching, the influence of p-doping on the NW morphology was investigated, and the results could be explained by the proposed model. In comparison with other c-axis NW transistors, an enhancement-mode (E-mode) operation with a superior threshold voltage ( V-th ) of 2.5 V has been reached in the fabricated GaN MOSFETs. Furthermore, a high driving-current density of 101 kA/cm2 as well as a high ON-/OFF-current ratio of 109 was obtained in the NWs, predicting a potential approach toward future GaN electronics with vertical and smart architecture.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Enhancement mode (E-mode); GaN nanowire (NW); logic circuit; MOSFET; switching; top-down; vertical transistor

Novel ultrafast vertically emitting semiconductor lasers - Pallmann, W. P.; Hoffmann, M.; Wittwer, V. J.; Rudin, B.; Kreuter, P.; Witzigmann, Bernd; Golling, M.; Barbarin, Y.; Südmeyer, T.; Keller, U. (European Conference on Optical Communication, ECOC, 2010)
We demonstrate the highest average power of any modelocked semiconductor laser: the optically-pumped MIXSEL generates 6.4-W in 28.1-ps pulses at 2.5-GHz repetition rate. Furthermore, we discuss electrically-pumped VECSELs optimized for passive modelocking and present initial cw-lasing with >100-mW. ©2010 IEEE.
CRIS-Team Scopus Importer:2021-06-11

n-type Ge/Si antennas for THz sensing - Chavarin, C. A.; Hardt, E.; Gruessing, S.; Skibitzki, O.; Costina; Spirito, Davide; Seifert, W.; Klesse, W.; Manganelli, C. L.; You, C.; Flesch, J.; Piehler, J.; et al. (Optics Express, 2021)
Ge-on-Si plasmonics holds the promise for compact and low-cost solutions in the manipulation of THz radiation. We discuss here the plasmonic properties of doped Ge bow-tie antennas made with a low-point cost CMOS mainstream technology. These antennas display resonances between 500 and 700 GHz, probed by THz time domain spectroscopy. We show surface functionalization of the antennas with a thin layer of α-lipoic acid that red-shifts the antenna resonances by about 20 GHz. Moreover, we show that antennas protected with a silicon nitride cap layer exhibit a comparable red-shift when covered with the biolayer. This suggests that the electromagnetic fields at the hotspot extend well beyond the cap layer, enabling the possibility to use the antennas with an improved protection of the plasmonic material in conjunction with microfluidics.
CRIS-Team Scopus Importer:2021-06-11

Numerical analysis of subwavelength field effects in photonic crystal slab cavities - Mertin, Paul; Roemer, Friedhard; Witzigmann, Bernd (JPhys Photonics, 2020)
Surface coupling of single quantum emitters to optical cavities consisting of a photonic crystal slab is a delicate yet crucial task for photonic quantum applications. By coupling through the evanescent surface field only small Purcell factors can be achieved. Here, we propose to introduce a pit in the slab to position the emitter closer to the mode field maximum. Photonic crystal slab L3 cavities are investigated with respect to quality factor and Purcell effect, using finite element calculations in the frequency domain. That way the spatial distribution of the Purcell factor can be calculated. Introducing a small sized pit to the surface of the photonic crystal cavity can evoke subwavelength field effects, confining the field maximum inside the pit. By engineering a pit in the center of the cavity the Purcell factor can be increased from 176 to 1331, albeit reducing the Q factor from 20769 to 16696.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Emitter-cavity coupling; Numerical simulation; Optical cavity; Photonic crystals

On the uncertainty of the Auger recombination coefficient extracted from InGaN/GaN light-emitting diode efficiency droop measurements - Piprek, Joachim; Roemer, Friedhard; Witzigmann, Bernd (Applied Physics Letters, 2015)
III-nitride light-emitting diodes (LEDs) suffer from a severe efficiency reduction with increasing injection current (droop). Auger recombination is often seen as primary cause of this droop phenomenon. The corresponding Auger recombination coefficient C is typically obtained from efficiency measurements using mathematical models. However, C coefficients reported for InGaN active layers vary over two orders of magnitude. We here investigate this uncertainty and apply successively more accurate models to the same efficiency measurement, thereby revealing the strong sensitivity of the Auger coefficient to quantum well properties such as electron-hole ratio, electric field, and hot carrier escape.
CRIS-Team Scopus Importer:2021-06-11

Optical anisotropy in semipolar (Al,In)GaN laser waveguides - Scheibenzuber, W.; Schwarz, U.; Veprek, R.; Witzigmann, Bernd; Hangleiter, Andreas (Physica Status Solidi (C) Current Topics in Solid State Physics, 2010)
In this work, the optical eigenmodes of a semipolar (Al,In)GaN laser diode are calculated. A full vectorial one-dimensional 4x4 transfer matrix method is used to correctly incorporate the influence of birefringence of the wurtzite crystal. Depending on the orientation of the laser waveguide relative to the c-axis, the eigenmodes show TE/TM- or extraordinary/ordinary polarization. The polarization direction of the eigenmodes is crucial for the performance of the laser, as it determines the relevant interband matrix elements for the optical gain. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA.
CRIS-Team Scopus Importer:2021-06-11
Keywords: (Al; In)GaN; Laser; Optical properties; Waveguides

Optical characterization of photonic crystals as polarizing structures for tunable optical MEMS devices - Zamora, R.; Benes, M.; Kusserow, T.; Hillmer, H.; Akcakoca, U.; Witzigmann, Bernd (International Conference on Optical MEMS and Nanophotonics, 2011)
We present 2D Photonic Crystals fabricated in an InP membrane to provide polarization selectivity to InP/Air-gap Fabry-Pérot filters. The characterization setup and preliminary results of the polarization properties of the photonic crystal structure are reported. © 2011 IEEE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: InP Membrane; Micromachined Tunable Fabry-Pérot Filters; Optical Characterization; Photonic Crystals; Polarization Selectivity

Optical Gain in AlGaN Quantum Wells: Impact of Higher Energy States - Kölle, Sebastian; Römer, Friedhard; Cardinali, Giulia; Schulz, Alexander; Susilo, Norman; Hauer Vidal, Daniel; Wernicke, Tim; Kneissl, Michael; Witzigmann, Bernd (IEEE Photonics Journal, 2024)
Simulations of optical gain in aluminum gallium nitride (AlGaN) quantum wells are extended to the high charge carrier density regime required for achieving gain at 275 nm for UV laser diodes. Coulomb interaction is modeled using the 2nd Born approximation. We demonstrate good agreement with experimental data obtained through optical pumping, and predict gain spectra for electrical pumping. Special consideration is given to the contribution of higher bands in wide quantum well
CRIS-Team Scopus Importer:2024-03-29
Keywords: Aluminum gallium nitride; Aluminum gallium nitride; Charge carrier density; Optical pumping; Optical waveguides; Optoelectronic devices; Quantum well lasers; Scattering; Simulation; Stimulated emission; Wide band gap semiconductors

Optical properties of individual GaN nanorods for light emitting diodes: Influence of geometry, materials, and facets - Koelper, C.; Sabathil, M.; Witzigmann, Bernd; Roemer, F.; Bergbauer, W.; Strassburg, M. (Proceedings of SPIE - The International Society for Optical Engineering, 2011)
We present a systematic analysis of the optical properties of GaN nanorods (NRs) for the application in Light Emitting Diodes (LEDs). Our focus is on NR emitters incorporating active layers in the form of quantum-disc or core-shell geometries. We concentrate on the properties of individual NRs, neglecting any coupling with neighbouring NRs or ensemble effects. The distribution of power among guided and radiative modes as well as Purcell enhancement is discussed in detail in the context of different NR geometries, materials and the presence of interfaces. © 2011 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Beam shaping; Extraction efficiency; GaN; LED; Nanorods; Nitrides; Optical waveguide; Purcell effect

Optimization of 1.55 µm quantum dot edge-emitting lasers for narrow spectral linewidth - Bjelica, Marko; Witzigmann, Bernd (Optical and Quantum Electronics, 2016)
Quantum dots are well known as active laser materials with remarkable properties such as high differential gain, low linewidth enhancement factor and low threshold current density. In this paper we use a comprehensive traveling wave based laser model to investigate the spectral linewidth of quantum dot edge-emitting lasers for use in high bit rate optical communications. By systematic optimization of the resonant cavity design we reach linewidths of below 10 kHz, which is a reduction by an order of magnitude compared to classical distributed feedback laser designs.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Quantum dot; Semiconductor laser; Spectral linewidth; Traveling wave

Optimized VCSELs for high-power arrays - Moench, Holger; Kolb, Johanna S.; Engelhardt, Andreas P.; Gerlach, Philipp; Jaeger, Roland; Pollmann-Retsch, Jens; Weichmann, Ulrich; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
High-power VCSEL systems with multi kilowatt output power require a good electro-optical efficiency at the point of operation i.e. at elevated temperature. The large number of optimization parameters can be structured in a way that separates system and assembly considerations from the minimization of electrical and optical losses in the epitaxially grown structure. Temperature dependent functions for gain parameters, internal losses and injection efficiency are derived from a fit to experimental data. The empirical description takes into account diameter dependent effects like current spreading or temperature dependent ones like voltage drops over hetero-interfaces in the DBR mirrors. By evaluating experimental measurements of the light output and voltage characteristics over a large range of temperature and diameter, wafer-characteristic parameters are extracted allowing to predict the performance of VCSELs made from this material in any array and assembly configuration. This approach has several beneficial outcomes: Firstly, it gives a general description of a VCSEL independent of its geometry, mounting and detuning, secondly, insights into the structure and the underlying physics can be gained that lead to the improvement potential of the structure and thirdly the performance of the structure in arrays and modules can be predicted. Experimental results validate the approach and demonstrate the significantly improved VCSEL efficiency and the benefit in high power systems. © 2014 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: DBR losses; electro-optical optimization; High Power VCSEL System; semiconductor hetero-interfaces; VCSEL array; Vertical-Cavity Surface-Emitting Laser; wafer-characteristic parameters

Performance analysis and simulation of vertical gallium nitride nanowire transistors - Witzigmann, Bernd; Yu, Feng; Frank, Kristian; Strempel, Klaas; Fatahilah, Muhammad Fahlesa; Schumacher, Hans Werner; Wasisto, Hutomo Suryo; Roemer, Friedhard; Waag, Andreas (Solid-State Electronics, 2018)
Gallium nitride (GaN) nanowire transistors are analyzed using hydrodynamic simulation. Both p-body and n-body devices are compared in terms of threshold voltage, saturation behavior and transconductance. The calculations are calibrated using experimental data. The threshold voltage can be tuned from enhancement to depletion mode with wire doping. Surface states cause a shift of threshold voltage and saturation current. The saturation current depends on the gate design, with a composite gate acting as field plate in the p-body device.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Gallium nitride; Nanowires; Simulation; Transistor

Physics-based simulation of a core-multishell nanowire light emitting diode - Römer, Friedhard; Deppner, Marcus; Witzigmann, Bernd (10th International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD 2010, 2010)
We report on the computational analysis of a triangular core-multishell nanowire light emitting diode with three joint InxGa1-xN active layers. The different crystal orientations of these layers lead to different polarization induced internal fields and transition energies. The simulation approach accounts for these effects by including the calculation of strained band edges and piezo potentials and provides a self-consistent model for the coupled 3D bulk and 2D quantized structure. The simulator is targeted to a comprehensive analysis of luminescence including the spatial variation of transition energies and carrier densities. ©2010 IEEE.
CRIS-Team Scopus Importer:2021-06-11

Planar Semiconductor THz Antennas Using Spoof Plasmons for Surface Sensing - Bettenhausen, Maximilian; Römer, Friedhard; Witzigmann, Bernd; Flesch, Julia; Piehler, Jacob; You, Changjiang; Kazmierczak, Marcin; Guha, Subhajit; Capellini, Giovanni; Schröder, Thomas (IEEE MTT-S International Microwave Symposium Digest, 2018)
Spoof surface plasmons are bound electromagnetic modes that are formed on corrugated metal surfaces. In particular for Teraheartz operating frequencies they allow subwavelength electromagnetic confinement. Their dispersion relation can be controlled by their geometric parameters of subwavelength grooves. In this letter a novel semiconductor design for spoof plasmons with patterned doping and a planar surface is presented. This design shows a higher field confinement and sensitivity compared to a plasmonic semiconductor with constant doping or metallic spoof plasmons.
CRIS-Team Scopus Importer:2021-06-11
Keywords: plasmonic antennas; semidonductor plasmonics; spoof plasmons; terahertz

Plasmonic germanium resonators for CMOS compatible Terahertz chem-bio sensing platform - Guha, S.; Kazmierczak, M.; Betthenhausen, M.; Skibitzki, O.; You, C.; Mitzloff, J.; Flesch, J.; You, C.; Piehler, J.; Witzigmann, Bernd; Schroeder, T. (14th International Conference on Group IV Photonics, GFP 2017, 2017)
Plasmon resonance based biosensors are considered as one of the most sensitive bio detection methods, in which the sensitivity is of the order of a single biomolecule due to extremely high enhancement of the electromagnetic field. Although established metal plasmonic biosensors are extremely sensitive, they suffer from integration issues due to non-compatibility to standard semiconductor fabrication technology (CMOS technology) [1]. Additionally, metal plasmonic sensors operate in the Near IR to visible spectral range, therefore, essentially leaving a gap in the Terahertz (THz) spectral regime which is interesting for biological applications like detection of conformational changes in proteins. On the other hand, doped semiconductor materials show plasmonic behaviour in the THz spectral regime [1, 2], and can be integrated on standard semiconductor foundry processes. This work demonstrates plasmon based Germanium (Ge) resonators fabricated on standard BiCMOS technology operating at THz frequency range for chem-bio sensing.
CRIS-Team Scopus Importer:2021-06-11

Plasmonic Perfect Absorbers for Biosensing Applications - Jamali, Abdul Aleem; Witzigmann, Bernd (Plasmonics, 2014)
We present a theoretical modal investigation of plasmonic perfect absorbers (PPAs) based on the localized surface plasmon resonance (LSPR) for biosensing applications. We design the PPA geometry with a layer of periodic metallic nanoparticles on one side of a dielectric substrate and a single metallic layer on the opposite side. The electromagnetic (EM) fields confine partly in the surrounding medium above the substrate and within the substrate itself. We examine the modes of the PPA geometry for a wavelength range of 600–1500 nm. The fundamental mode of the system provides perfect absorption for a wide angle of incidence 0–70°. The second-order mode shows a strong angular dependence with a sharp resonance and exhibits perfect optical absorption when the critical coupling condition for LSPR is achieved. The coupling condition depends on the size, periodicity, dielectric spacer, and the surrounding material of the system. The strong dependence on the surrounding material makes it a promising candidate for biosensing applications. We introduce a novel approach to investigate the angular dependence of the refractive index change for the PPA system. This novel technique contributes the significant attributes of the LSPR sensors, can be used for any required resonance wavelength depending on geometric design, and it also provides sensitivity analogous to the standard surface plasmon resonance (SPR) biosensors.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Biosensors; Localized surface plasmon resonance (LSPR); Plasmonic perfect absorbers (PPAs); Plasmonics; Surface plasmon resonance (SPR)

Polarization induced doping for carrier transport in graded III-nitride layers: a simulation study - Witzigmann, Bernd; Römer, Friedhard (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
Hexagonal III-nitride semiconductors exhibit internal polarization fields along their c-direction. In regions with graded mole fractions, the polarization gradient creates bound volume charge densities. Due to their electrostatic effect, they affect the balance of mobile charges, and can lead to polarization induced doping. In this contribution, drift-diffusion type simulations are employed in order to analyze a pn-junction based on polarization induced charges, and an analytical formula for calculating the bound charge density is given.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Carrier Transport; Doping; III-Nitride

Polarization of eigenmodes in laser diode waveguides on semipolar and nonpolar GaN - Rass, Jens; Wernicke, Tim; Scheibenzuber, Wolfgang G.; Schwarz, Ulrich T.; Kupec, Jan; Witzigmann, Bernd; Vogt, Patrick; Einfeldt, Sven; Weyers, Markus; Kneissl, Michael (Physica Status Solidi-Rapid Research Letters, 2010)
Recent calculations of the eigenmodes in waveguides grown on semipolar GaN suggest that the optical polarization of the emitted light as well as the optical gain depends on the orien- tation of the resonator. Our measurements on separate confinement heterostructures on semipolar (1122) and (1012) GaN show that for laser resonators along the semipolar [1123] and [0111] directions (i.e. the projection of the c-axis onto the plane of growth) the threshold for amplified spontaneous emission is lower than for the nonpolar direction and that the stimulated emission is linearly polarized as TE mode. For the waveguide structures along the nonpolar [1100] or [1120] direction on the other hand, birefringence and anisotropy of the optical gain in the plane of growth leads not only to a higher threshold but alsoto a rotation of the optical polarization which is not any more TE- or TM-polarized but influenced by the ordinary and extraordinary refractive index of the material. We observe stimulated emission into a mode which is linearly polarized in extraordinarydirection nearly parallel to the c-axis.© 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2021-06-11

Precise determination of polarization fields in c-plane GaN/AlxGa1-xN/GaN heterostructures with capacitance-voltage-measurements - Susilo, Norman; Schilling, Marcel; Narodovitch, Michael; Yao, Hsin-Hung; Li, Xiaohang; Witzigmann, Bernd; Enslin, Johannes; Guttmann, Martin; Roumeliotis, Georgios G.; Rychetsky, Monir; Koslow, Ingrid; Wernicke, Tim; et al. (Japanese Journal of Applied Physics, 2019)
Due to changes in the spontaneous and piezoelectric polarization, AlGaN/GaN heterostructures exhibit strong polarization fields at heterointerfaces. For quantum wells, the polarization fields lead to a strong band bending and a redshift of the emission wavelength, known as quantum-confined Stark effect. In this paper the polarization fields of thin AlGaN layers in a GaN matrix were determined by evaluating the changes in the depletion region width in comparison to a reference sample without heterostructure using capacitance-voltage-measurements. The polarization fields for Al0.09Ga0.91N (0.6 ±0.7 MV cm-1), Al0.26Ga0.74N (2.3 ±0.6 MV cm-1), Al0.34Ga0.66N (3.1 ±0.6 MV cm-1), Al0.41Ga0.59N (4.0 ±0.7 MV cm-1) and Al0.47Ga0.53N (5.0 ±0.8 MV cm-1) heterostructures were determined. The results of the field strength and field direction of all samples are in excellent agreement with values predicted by theory and a capacitance-voltage based Poisson-carrier transport simulation approach giving experimental evidence for a nonlinear increasing polarization field with Al-concentration.
CRIS-Team Scopus Importer:2021-06-11

Quantitative protein sensing with germanium THz-antennas manufactured using CMOS processes - Hardt, Elena; Chavarin, Carlos Alvarado; Gruessing, Soenke; Flesch, Julia; Skibitzki, Oliver; Spirito, Davide; Vita, Gian Marco; Simone, Giovanna D.E.; Masi, Alessandra D.I.; You, Changjiang; Witzigmann, Bernd; Piehler, Jacob; et al. (Optics Express, 2022)
The development of a CMOS manufactured THz sensing platform could enable the integration of state-of-the-art sensing principles with the mixed signal electronics ecosystem in small footprint, low-cost devices. To this aim, in this work we demonstrate a label-free protein sensing platform using highly doped germanium plasmonic antennas realized on Si and SOI substrates and operating in the THz range of the electromagnetic spectrum. The antenna response to different concentrations of BSA shows in both cases a linear response with saturation above 20 mg/mL. Ge antennas on SOI substrates feature a two-fold sensitivity as compared to conventional Si substrates, reaching a value of 6 GHz/(mg/mL), which is four-fold what reported using metal-based metamaterials. We believe that this result could pave the way to a low-cost lab-on-a-chip biosensing platform.
CRIS-Team Scopus Importer:2022-11-04

Quantum Information Interface on a Photonic Crystal Chip - Mertin, Paul; Witzigmann, Bernd (2021 INTERNATIONAL CONFERENCE ON NUMERICAL SIMULATION OF OPTOELECTRONIC DEVICES (NUSOD), 2021)
CRIS-Team WoS Importer:2021-12-10

Red surface-emitting SLEDs - Jentzsch, Bruno; Gomez-Iglesias, Alvaro; Tonkikh, Alexander; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
Surface-emitting InGaAlP SLEDs that are based on in-plane amplification along a horizontal waveguide are demonstrated. Total internal reflection at tilted etched micromirrors are used for the deflection of optical modes normal to the chip surface. Applying a bonding process of the etched wafer onto a new carrier, light can be emitted through the surface that was originally covered by the growth substrate. Depending on the waveguide geometry superluminescence as well as lasing operation is observed. In superluminescence operation an emission spectrum with a FWHM of 10nm centered at 637nm is obtained. The peak output power of the amplified spontaneous emission is up to ∼ 200mW which corresponds to a WPE of ∼ 6 %. In case of lasing (λ ∼ 639 nm) a peak output power larger than 1000mW at a WPE that exceeds 20% is achieved. In addition, an array configuration with radially aligned waveguides that contribute to a common far field is investigated as well.
CRIS-Team Scopus Importer:2021-06-11
Keywords: InGaAlP; Red; SLED; Superluminescent Diode; Surface-Emission

SESAM-modelocked electrically pumped VECSELs emitting 6.3-ps pulses - Zaugg, C. A.; Pallmann, W. P.; Mangold, M.; Dahhan, I.; Golling, M.; Tilma, B. W.; Witzigmann, Bernd; Keller, U. (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
Optically pumped vertical external cavity surface emitting lasers (OP-VECSELs) evolved to high-power laser sources offering excellent beam-quality, wavelength flexibility and low-noise properties in a compact and simple cavity. Passively modelocked with a semiconductor saturable absorber mirror (SESAM), VECSELs demonstrated fs-pulses with multi-Watt average output powers at gigahertz repetition rates. Electrical pumping (EP) is an obvious step to make these semiconductor lasers even more compact and suitable for chip integration, potentially enabling access to applications such as data communication or optical clocking. With SESAMmodelocked EP-VECSELs, 57-ps pulses with an average output power of 40 mW and 9.5-ps pulses with 7.6 mW have been obtained. However, due to the intrinsic trade-off between electrical and optical properties in the design of EPVECSELs, short pulses at high average output power are difficult to achieve. This challenge was previously addressed in our theoretical guidelines for power scaling and modelocking optimization and later experimentally verified. Here, we report on the successful implementation of an improved design and fabrication scheme for EP-VECSELs, grown and fabricated at ETH Zurich. These lasers enabled a further decrease in pulse duration to 7.3 ps while increasing the average output power to 13.1 mW at 1.46-GHz repetition rate. The shortest pulse duration measured was 6.3 ps with an average power of 6.2 mW. In addition to the modelocking experiments, we present a thorough cw-characterization of our EP-VECSELs of different sizes and in different cavity configurations, pointing out the inevitable trade-off between high-power multi-mode and low-power single-mode operation limiting the modelocking performance. © 2014 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Diode lasers; Infrared lasers; Modelocked lasers; Semiconductor lasers; Ultrafast lasers; Vertical emitting lasers

Signature of the ideality factor in III-nitride multi quantum well light emitting diodes - Römer, Friedhard; Witzigmann, Bernd (Optical and Quantum Electronics, 2017)
The ideality factor in recent III-nitride light emitting diodes (LED) is expected to approach values close to η≈ 1 near the maximum of the internal quantum efficiency (IQE) because the bimolecular recombination dominates there. However, the electrical characterisation of multi quantum well (MQW) LEDs often yields values which are more close to η≈ 2 or even more. To analyse the effect of the MQW on the ideality factor we derive an electrical model based on lumped circuit elements. By comparing the model results with the physical simulations of the ideality factor we demonstrate its validity. The detailed analysis of the circuit elements reveals that the electron scattering has a major impact on the ideality factor near the maximum of the IQE. We show that the ideality factor presents a signature for the hole injection efficiency and thus can be used to estimate the IQE characteristic in the high current regime.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Carrier transport simulation; Ideality factor; III-Nitride; Light emitting diode; Multi quantum well

Simulation and analysis of 1.55μm quantum dot lasers designed for ultra-narrow spectral linewidth - Bjelica, Marko; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2015)
Quantum dots (QDs) are well known as active materials with remarkable properties such as high differential gain, very low linewidth enhancement factor and low threshold current density. Using a comprehensive in-house developed laser simulator based on the traveling wave method, we investigate the limitations in terms of spectral purity of quantum dot based distributed feedback lasers (DFB) for use in high bit rate optical communications. Even though quantum dot based edge emitting lasers have demonstrated linewidths below the standard quantum well and bulk lasers, by optimization of the resonant cavity we further reduce the linewidth to below 20KHz while studying the resulting operating conditions.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Cavity resonators; Charge carrier density; Mathematical model; Optical feedback; Optical modulation; Quantum dot lasers; Standards

Simulation, design, and characterization of electrically-pumped VECSELs for future passive modelocking - Hoffmann, M.; Barbarin, Y.; Pallmann, W. P.; Maas, D. J.H.C.; Kreuter, P.; Witzigmann, Bernd; Golling, M.; Südmeyer, T.; Keller, U. (Optics InfoBase Conference Papers, 2010)
An ultrafast electrically-pumped VECSEL design requires an acceptable trade-off in cw output power. Validating our design guidelines and simulations 120 mW cw output power are generated. Homogenous current injection is even achieved for large devices. © 2009 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-11

Simulation of an indium gallium nitride quantum well light-emitting diode with the non-equilibrium Green's function method - Shedbalkar, Akshay; Andreev, Zhelio; Witzigmann, Bernd (physica status solidi (b), 2016)
This work presents a quantum mechanical simulation of an indium gallium nitride (InGaN) based light-emitting diode (LED) using the non-equilibrium Green's function (NEGF) method. Due to the wurtzite crystal structure, such LEDs exhibit strong polarization-induced electric fields at heterointerfaces. Standard simulation methods based on the drift-diffusion (DD) model do not take into account potentially important transport mechanisms such as quantum mechanical tunneling or non-equilibrium carrier distributions in the device. These effects are included in the NEGF model, while the semi-classical models employ parametrized approximations. In principle, the NEGF simulation therefore allows a more realistic view of the physical process that take place in the LEDs.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Contacts; GaN; Light-emitting diodes; Minority carriers; Non-equilibrium Green's function method; Optoelectronics

Simulation of Carrier Injection Efficiency in AlGaN-based UV-light-emitting Diodes - Hofmann, Gregor; Muhin, Anton; Susilo, Norman; Römer, Friedhard; Wernicke, Tim; Kneissl, Michael; Witzigmann, Bernd (IEEE Photonics Journal, 2024)
Numerical simulations of carrier transport in aluminium gallium nitride based ultraviolet light emitting diodes (UV-LED) are performed in order to understand injection efficiency for light sources in the deep ultraviolet. With our simulator, calibrated with experimental data from a 265 nm UV-LED, quantum efficiencies have been analyzed. The maximum internal quantum efficiency (IQE) of 30% consists of the product from radiative recombination efficiency (RRE) of 60% and carrier injection efficiency (CIE) of 50%. It is found that poor hole injection into the active region and a surplus of electrons limit both efficiencies, and leads to significant electron leakage into the p-side. This leakage is bias dependent, and has a minimum at maximum IQE. Further simulations show that distributed polarization doping (DPD) could improve carrier injection efficiency.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Current density; Doping; Efficiency; Gallium; Gallium Nitride; LED; Light Emitting Diode; Light emitting diodes; Light Source; Mathematical models; Modeling; Radiative recombination; Semiconductor process modeling

Simulation of InGaN quantum well LEDs with reduced internal polarization - Andreev, Zhelio; Roemer, Friedhard; Witzigmann, Bernd (physica status solidi (a), 2012)
This work presents a theoretical comparison of efficiency in III-nitride light emitting diodes (LEDs). We simulate non-, semi-, and polar devices, and analyze their I-V characteristics and internal quantum efficiencies (IQEs). In addition we present simulations of a new structural design for nitride devices, with decreased polarization charges, using quaternary AlInGaN material. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2021-06-11
Keywords: efficiency; LEDs; nitride; quaternary; simulations

Simulation of optical gain in AlGaN quantum wells - Kolle, S.; Römer, Friedhard; Cardinali, G.; Schultz, A.; Susilo, N.; Vidal, D. Hauer; Wernicke, T.; Kneissl, M.; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2023)
Simulations of optical gain in aluminum gallium nitride (AlGaN) quantum wells are extended to the high charge density regime required for achieving gain at 275 nm for UV laser diodes. Coulomb interaction is modeled using the 2nd Born approximation. We demonstrate good agreement with experimental data obtained through optical pumping, and predict gain spectra for electrical pumping.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Aluminum gallium nitride; Optoelectronic devices; Quantum well lasers; Simulation

Simulation of water photo electrolysis with III-nitride semiconductor nano wires - Witzigmann, Bernd; Bettenhausen, Maximilian; Mewes, Marvin; Fuele, Heiko; Roemer, Friedhard (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
Water splitting under illumination with a GaN/InGaN planar and nano wire structure is modeled using a drift diffusion approach. The main features of the experiment such as current density without biasing and current saturation effects are explained by the simulation. The electrolyte where ionic transport occurs is modeled as material with diffusion coefficients matching ionic diffusivity experiments. The simulation allows design and analysis of GaN based nano structures and their water photo electrolysis efficiency. © 2014 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Energy Harvesting; Gallium Nitride; Nano Wire; Simulation; Water Splitting

Simulation Study of Aluminum Nitride TrenchFETs with Polarization-Induced Doping - Faber, Samuel; Römer, Friedhard; Witzigmann, Bernd (physica status solidi (a), 2024)
Aluminum nitride (AlN) possesses a high critical electric field, allowing for thinner drift regions and lower resistances compared with current materials used for power semiconductor devices. However, high activation energies of impurity dopants like magnesium or silicon and high contact resistances impede the application of AlN for typical device concepts such as TrenchFET. This article aims to develop and investigate novel vertical device structures using an AlN drift region. To evade the aforementioned issues, polarization-induced doping is applied to generate an effective charge concentration and to accomplish less resistive ohmic contacts.
CRIS-Team Scopus Importer:2024-04-19
Keywords: aluminum gallium nitride; aluminum nitride; polarization-induced doping; TrenchFET

Spectral Characteristics of Narrow Linewidth InAs/InP Quantum Dot Distributed Feedback Lasers - Septon, Tali; Gosh, Sutapa; Becker, Annette; Eyal, Ori; Bjelica, Marco; Sichkovskyi, Vitalii; Rippien, Anna; Schnabel, Florian; Witzigmann, Bernd; Reithmaier, Johann P.; Eisenstein, Gadi (Conference Digest - IEEE International Semiconductor Laser Conference, 2018)
We report spectral characteristics of InAs/InP QD DFB lasers. Owing to low linewidth enhancement factor and high modal gain, lasers with 5 QD layers exhibit record linewidth of 55 kHz measured by the heterodyne beat note between the laser and an ultra-stable optical frequency comb.
CRIS-Team Scopus Importer:2021-06-11

Spectrally Tunable Broadband Gate-All-Around InAsP/InP Quantum Discs-in-Nanowire Array Phototransistors with a High Gain-Bandwidth Product - Jeddi, Hossein; Witzigmann, Bernd; Adham, Kristi; Hrachowina, Lukas; Borgstrom, Magnus T.; Pettersson, Håkan (ACS Photonics, 2023)
High-performance broadband photodetectors offering spectral tunability and a high gain-bandwidth product are crucial in many applications. Here, we report on a detailed experimental and theoretical study of three-terminal phototransistors comprised of three million InP nanowires with 20 embedded InAsP quantum discs in each nanowire. A global, transparent ITO gate all around the nanowires facilitates a radial control of the carrier concentration by more than two orders of magnitude. The transfer characteristics reveal two different transport regimes. In the subthreshold region, the photodetector operates in a diffusion mode with a distinct onset at the bandgap of InP. At larger gate biases, the phototransistor switches to a drift mode with a strong contribution from the InAsP quantum discs. Besides an unexpected spectral tunability, the detector exhibits a state-of-the-art responsivity, reaching around 100 A/W (638 nm/20 µW) @ VGS = 1.0 V/VDS = 0.5 V with a gain-bandwidth product of around 1 MHz, in excellent agreement with a comprehensive real-device model.
CRIS-Team Scopus Importer:2023-07-07
Keywords: gate-all-around contacts; infrared photodetectors; interface traps; nanowire array phototransistors; nanowires; photogating; quantum discs-in-nanowires

Stable and selective self-assembly of α-lipoic acid on Ge(001) for biomolecule immobilization - Kazmierczak, M.; Flesch, J.; Mitzloff, J.; Capellini, Giovanni; Klesse, W. M.; Skibitzki, O.; You, Changjiang; Bettenhausen, M.; Witzigmann, Bernd; Piehler, J.; Schroeder, T.; Guha, S. (Journal of Applied Physics, 2018)
We demonstrate a novel method for the stable and selective surface functionalization of germanium (Ge) embedded in silicon dioxide. The Ge(001) surface is functionalized using α-lipoic acid (ALA), which can potentially be utilized for the immobilization of a wide range of biomolecules. We present a detailed pH-dependence study to establish the effect of the incubation pH value on the adsorption layer of the ALA molecules. A threshold pH value for functionalization is identified, dividing the examined pH range into two regions. Below a pH value of 7, the formation of a disordered ALA multilayer is observed, whereas a stable well-ordered ALA mono- to bi-layer on Ge(001) is achieved at higher pH values. Furthermore, we analyze the stability of the ALA layer under ambient conditions, revealing the most stable functionalized Ge(001) surface to effectively resist oxidation for up to one week. Our established functionalization method paves the way towards the successful immobilization of biomolecules in future Ge-based biosensors.
CRIS-Team Scopus Importer:2021-06-11

Structuring of 2D photonic crystal on InP membranes as polarizing element for optical MEMS based sensor systems - Zamora, R.; Kusserow, T.; Wulf, M.; Kanwar, K.; Witzigmann, Bernd; Hillmer, H. (INSS 2010 - 7th International Conference on Networked Sensing Systems, 2010)
Narrow band Fabry-Ṕrot MEMS filters are investigated for the integration in optical fiber sensor networks. We present a technological process to implement a 2D photonic crystal (PhC) structure on an InP membrane, in order to provide an InP/air-gap Fabry-Ṕrot filter with polarization selectivity. The capabilities and limitations of Focused Ion Beam (FIB) lithography combined with Reactive Ion Etching (RIE) are investigated to fabricate the PhC structure. Special focus is given to the etching rate of the required hard mask, utilized in the FIB lithography, to determine the optimal thickness to produce high quality structures. Additionally, the mechanical properties of the PhC membrane and the influence on the basic filter structure are investigated. © 2010 IEEE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Fabry-Perot filter; FIB lithography; Fiber based sensor networks; Photonic crystals; Polarization selectivity; RIE

Study of photocurrent generation in InP nanowire-based p+-i-n+ photodetectors - Jain, Vishal; Nowzari, Ali; Wallentin, Jesper; Borgstrom, Magnus T.; Messing, Maria E.; Asoli, Damir; Graczyk, Mariusz; Witzigmann, Bernd; Capasso, Federico; Samuelson, Lars; Pettersson, Hakan (Nano Research, 2014)
We report on electrical and optical properties of p+-i-n+ photodetectors/solar cells based on square millimeter arrays of InP nanowires (NWs) grown on InP substrates. The study includes a sample series where the p+-segment length was varied between 0 and 250 nm, as well as solar cells with 9.3% efficiency with similar design. The electrical data for all devices display clear rectifying behavior with an ideality factor between 1.8 and 2.5 at 300 K. From spectrally resolved photocurrent measurements, we conclude that the photocurrent generation process depends strongly on the p+-segment length. Without a p+-segment, photogenerated carriers funneled from the substrate into the NWs contribute strongly to the photocurrent. Adding a p+-segment decouples the substrate and shifts the depletion region, and collection of photogenerated carriers, to the NWs, in agreement with theoretical modeling. In optimized solar cells, clear spectral signatures of interband transitions in the zinc blende and wurtzite InP layers of the mixed-phase i-segments are observed. Complementary electroluminescence, transmission electron microscopy (TEM), as well as measurements of the dependence of the photocurrent on angle of incidence and polarization, support our interpretations. [Figure not available: see fulltext.] © 2014 Tsinghua University Press and Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2021-06-11
Keywords: infrared (IR); nanophotonics; nanowires; photodetectors; solar cells

Surface-Emitting Micro-Mirror Superluminescent Diodes: Investigation of Tilt Accuracy Via Far-Field Analysis - Jentzsch, Bruno; Gomez-Iglesias, Alvaro; Tonkikh, Alexander; Zull, Heribert; Kugler, Siegmar; Witzigmann, Bernd (physica status solidi (b), 2019)
Far-field characteristics of novel surface-emitting micro-mirror superluminescent diodes are investigated. The mirrors are fabricated by using thin film technology and an inductively coupled plasma etching process on wafer scale, suitable for mass production. Combining measurements and modeling results, the mirror tilt is estimated and the feasibility of good-quality ≈45° mirrors is demonstrated. This approach offers an accuracy better than optical inspection with, e.g., scanning electron microscopy. In addition, our experiments revealed spurious ripples in the far-field profiles with increasing tilt deviations, which finite-difference time-domain simulations identified as interference with back reflections. These results highlight the importance of tailored waveguides, high quality coatings, and precise mirror tilt to achieve maximal performance with surface-emitting in-plane semiconductor devices.
CRIS-Team Scopus Importer:2021-06-11
Keywords: dry etched mirror; far field; superluminescent diode; surface emission; thin film technology

Surface-emitting superluminescent diode arrays - Jentzsch, Bruno; Gomez-Iglesias, Alvaro; Tonkikh, Alexander; Witzigmann, Bernd (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Superluminescent diodes (SLEDs) are typically edge-emitters based on in-plane amplified spontaneous emission and require low feedback to suppress lasing [1]. These devices are especially suited for applications demanding low temporal coherence and high output power densities with high directionality. To date SLEDs in the IR, as well as red, blue, and recently green have been reported [2].
CRIS-Team Scopus Importer:2021-06-11

Tdkp/AQUA: Unified modeling of electroluminescence in nanostructures - Steiger, Sebastian; Veprek, Ratko G.; Witzigmann, Bernd (Optical and Quantum Electronics, 2009)
This article summarizes the capabilities of the optoelectronic simulation framework tdkp/AQUA aimed at the description of electroluminescence in semiconductor nanostructures such as light-emitting diodes. tdkp is a stand-alone finite-element software able to accurately calculate strain, built-in fields due to spontaneous and piezoelectric polarization, bound quantum states using k · p theory, gain and luminescence spectra in zero-to three-dimensional structures. AQUA calculates transport through nanostructures using a model which accounts for the distinct behaviour of carriers confined to active regions and unconfined carriers. Furthermore, it computes electroluminescence spectra via a self-consistent coupling of the confined carriers to quantum-mechanical calculations using tdkp. Two examples are presented which highlight the versatility and generality of the developed framework. © Springer Science+Business Media, LLC. 2010.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Device simulation; Drift-diffusion; Electroluminescence; Kp theory; LED

tdkp/AQUA: Unified modelling of electroluminescence in nanostructures - Steiger, Sebastian; Veprek, Ratko G.; Witzigmann, Bernd (9th International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD 2009, 2009)
This article summarizes the capabilities of the optoelectronic simulation framework tdkp/AQUA aimed at the description of electroluminescence in semiconductor nanostructures such as light-emitting diodes (LEDs). tdkp is a standalone finite-element software able to accurately calculate strain, built-in fields due to spontaneous and piezoelectric polarization, quantum states, gain and luminescence spectra in zero- to three-dimensional structures. AQUA calculates transport through nanostructures using an original model which accounts for the distinct behaviour of carriers confined to active regions and unconfined carriers. Furthermore, it computes electroluminescence spectra via a self-consistent coupling of the confined carriers to quantum-mechanical calculations using tdkp. Two examples are presented which highlight the versatility and generality of the developed simulator. ©2009 IEEE.
CRIS-Team Scopus Importer:2021-06-11

Temperature dependent investigation of carrier transport, injection, and densities in 808 nm AlGaAs multi-quantum-well active layers for VCSELs - Engelhardt, Andreas P.; Kolb, Johanna S.; Roemer, Friedhard; Weichmann, Ulrich; Moench, Holger; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
The electro-optical efficiency of semiconductor vertical-cavity surface-emitting lasers (VCSELs) strongly depends on the efficient carrier injection into the quantum wells (QWs) in the laser active region. However, carrier injection degrades with increasing temperature which limits the VCSEL performance particularly in high power applications where self heating imposes high temperatures in operation. By simulation we investigate the transport of charge carriers in 808 nm AlGaAs multi-quantum-well active layers with special attention to the temperature dependence of carrier injection into the QWs. Experimental reference data was extracted from oxide-confined, top-emitting VCSELs. The transport simulations follow a drift-diffusion-model complemented by a customized, energy-resolved, semi-classical carrier capture theory. QW gain was calculated in the screened Hartree-Fock approximation with band structures from 8x8 k.p-theory. Using the gain data and by setting losses and the optical confinement factor according to experimental reference results, the appropriate threshold condition and threshold carrier densities in the QWs for a VCSEL are established in simulation for all transport considerations. With the combination of gain and transport model, we can explain experimental reference data for the injection efficiency and threshold current density. Our simulations show that the decreasing injection efficiency with temperature is not solely due to increased thermionic escape of carriers from the QWs. Carrier injection is also hampered by state filling in the QWs initiated from higher threshold carrier densities with temperature. Consequently, VCSEL properties not directly related to the active layer design like optical out-coupling or internal losses link the temperature dependent carrier injection to VCSEL mirror design. © 2014 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Carrier transport; Injection efficiency; Quantum well; Semiconductor modeling; State filling; Temperature dependence; Thermionic emission; VCSEL

Temperature-dependent investigation of carrier transport, injection, and densities in AlGaAs-based multi-quantum-well active layers for vertical-cavity surface-emitting lasers - Engelhardt, Andreas P.; Kolb, Johanna S.; Roemer, Friedhard; Weichmann, Ulrich; Moench, Holger; Witzigmann, Bernd (Optical Engineering, 2015)
The electro-optical efficiency of vertical-cavity surface-emitting lasers (VCSELs) strongly depends on the efficient carrier injection into the quantum wells (QWs) in the laser active region. Carrier injection degrades with increasing temperature, which limits VCSEL performance in high-power applications where self-heating imposes high-operating temperatures. In a numerical model, we investigate the transport of charge carriers in an 808-nm AlGaAs multi-quantum-well structure with special attention to the temperature dependence of carrier injection into the QWs. Experimental reference data were extracted from oxide-confined, top-emitting VCSELs. The transport simulations follow a drift-diffusion-model complemented by an energy-resolved carrier-capture model. The QW gain was calculated in the screened Hartree-Fock approximation. With the combination of the gain and transport model, we explain experimental reference data for the injection efficiency and threshold current. The degradation of the injection efficiency with increasing temperature is not only due to increased thermionic escape of carriers from the QWs, but also to state filling in the QWs initiated from higher threshold carrier densities. With a full opto-electro-thermal VCSEL model, we demonstrate how changes in VCSEL properties affecting the threshold carrier density, like mirror design or optical confinement, have consequences on the thermal behavior of the injection and the VCSEL performance.
CRIS-Team Scopus Importer:2021-06-11
Keywords: carrier transport; injection efficiency; state filling; temperature dependence; thermionic emission; vertical-cavity surface-emitting laser (VCSEL) modeling; vertical-cavity surface-emitting lasers (VCSEL)

Terahertz subwavelength sensing with bio-functionalized germanium fano-resonators - Chavarin, Carlos Alvarado; Hardt, Elena; Skibitzki, Oliver; Voss, Thomas; Eissa, Mohammed; Spirito, Davide; Capellini, Giovanni; Baldassarre, Leonetta; Flesch, Julia; Piehler, Jacob; You, Changjiang; Gruessing, Soenke; et al. (Frequenz, 2022)
Localized Surface Plasmon Resonances (LSPR) based on highly doped semiconductors microstructures, such as antennas, can be engineered to exhibit resonant features at THz frequencies. In this work, we demonstrate plasmonic antennas with increased quality factor LSPRs from Fano coupling to dark modes. We also discuss the advances in the biofunctionalization of n-doped Ge antennas for specific protein immobilization and cell interfacing. Finally, albumin biolayers with a thickness of a few hundred nanometers are used to demonstrate the performance of the fano-coupled n-Ge antennas as sensors. A resonant change of over 10% in transmission, due to the presence of the biolayer, can be detected within a bandwidth of only 20 GHz.
CRIS-Team WoS Importer:2022-08-26

The 2020 UV emitter roadmap - Amano, Hiroshi; Collazo, Ramon; Santi, Carlo De; Einfeldt, Sven; Funato, Mitsuru; Glaab, Johannes; Hagedorn, Sylvia; Hirano, Akira; Hirayama, Hideki; Ishii, Ryota; Kashima, Yukio; Kawakami, Yoichi; et al. (Journal of Physics D: Applied Physics, 2020)
Solid state UV emitters have many advantages over conventional UV sources. The (Al,In,Ga)N material system is best suited to produce LEDs and laser diodes from 400 nm down to 210 nm - due to its large and tuneable direct band gap, n- and p-doping capability up to the largest bandgap material AlN and a growth and fabrication technology compatible with the current visible InGaN-based LED production. However AlGaN based UV-emitters still suffer from numerous challenges compared to their visible counterparts that become most obvious by consideration of their light output power, operation voltage and long term stability. Most of these challenges are related to the large bandgap of the materials. However, the development since the first realization of UV electroluminescence in the 1970s shows that an improvement in understanding and technology allows the performance of UV emitters to be pushed far beyond the current state. One example is the very recent realization of edge emitting laser diodes emitting in the UVC at 271.8 nm and in the UVB spectral range at 298 nm. This roadmap summarizes the current state of the art for the most important aspects of UV emitters, their challenges and provides an outlook for future developments.
CRIS-Team Scopus Importer:2021-06-11
Keywords: AlGaN; InGaN; light emitting diodes; ultraviolet; UV-LED

Thermal performance analysis of GaN nanowire and fin-shaped power transistors based on self-consistent electrothermal simulations - Kamrani, Hamed; Yu, Feng; Frank, Kristian; Strempel, Klaas; Fatahilah, Muhammad Fahlesa; Wasisto, Hutomo Suryo; Roemer, Friedhard; Waag, Andreas; Witzigmann, Bernd (Microelectronics Reliability, 2018)
We present self-consistent electrothermal simulations of the GaN nanowire-based field-effect transistor (NWFET) and vertical fin field-effect transistor (FinFET) by taking into account all major heat flux paths. Simulation results of a NWFET validated by experimental data are compared to the results of a vertical FinFET designed with same sizes that ensures a fair comparison of their thermal performance. It is found that the peak temperature in the NWFET is close to the uppermost contact, which facilitates heat removal from top. As a result, NWFETs have the potential to achieve a higher power density at a temperature limit compared with the FinFETs, especially when the heat removal from the top contact is eased. The impact of the thermal surface resistance of the top contact and substrate thinning on the thermal performance of these two vertical structures is also investigated.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Electrothermal simulation; GaN nanowire field-effect transistor (NWFET); GaN vertical fin field-effect transistor (FinFET); Power transistors; Thermal performance

The ultra weak variational formulation applied to radiation problems with macroscopic sources in inhomogeneous domains - Loeser, Martin; Witzigmann, Bernd (IEEE Journal of Selected Topics in Quantum Electronics, 2009)
This paper shows the applicability of the ultraweak variational formulation for radiation problems that typically occur during the simulation of active optoelectronic devices. In frequency domain, we investigate the field generated by a macroscopic source (i.e., no point source) embedded in a layered medium with varying refractive index. The analysis focuses on large 2-D simulation domains up to 1000λ × 1000λ. A comparison with various reference solutions shows the applicability of the approach. Special focus is put on computational efficiency aspects such as information reduction and parallelization. © 2006 IEEE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: LED; Modeling; Multidimensional

Three-dimensional interfacing of cells with hierarchical silicon nano/microstructures for midinfrared interrogation of in situ captured proteins - Flesch, Julia; Bettenhausen, Maximilian; Kazmierczak, Marcin; Klesse, Wolfgang M.; Skibitzki, Oliver; Psathaki, Olympia E.; Kurre, Rainer; Capellini, Giovanni; Guha, Subhajit; Schroeder, Thomas; Witzigmann, Bernd; You, Changjiang; et al. (ACS Applied Materials and Interfaces, 2021)
Label-free optical detection of biomolecules is currently limited by a lack of specificity rather than sensitivity. To exploit the much more characteristic refractive index dispersion in the midinfrared (IR) regime, we have engineered three-dimensional IR-resonant silicon micropillar arrays (Si-MPAs) for protein sensing. By exploiting the unique hierarchical nano- and microstructured design of these Si-MPAs attained by CMOS-compatible silicon-based microfabrication processes, we achieved an optimized interrogation of surface protein binding. Based on spatially resolved surface functionalization, we demonstrate controlled three-dimensional interfacing of mammalian cells with Si-MPAs. Spatially controlled surface functionalization for site-specific protein immobilization enabled efficient targeting of soluble and membrane proteins into sensing hotspots directly from cells cultured on Si-MPAs. Protein binding to Si-MPA hotspots at submonolayer level was unambiguously detected by conventional Fourier transform IR spectroscopy. The compatibility with cost-effective CMOS-based microfabrication techniques readily allows integration of this novel IR transducer into fully fledged bioanalytical microdevices for selective and sensitive protein sensing.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Cell-sensor-interfacing; CMOS microfabrication; In situ protein immobilization; IR refractive index sensing; Label-free protein sensing

Top-down GaN nanowire transistors with nearly zero gate hysteresis for parallel vertical electronics - Fatahilah, Muhammad Fahlesa; Yu, Feng; Strempel, Klaas; Romer, Friedhard; Maradan, Dario; Meneghini, Matteo; Bakin, Andrey; Hohls, Frank; Schumacher, Hans Werner; Witzigmann, Bernd; Waag, Andreas; Wasisto, Hutomo Suryo (Scientific Reports, 2019)
This paper reports on the direct qualitative and quantitative performance comparisons of the field-effect transistors (FETs) based on vertical gallium nitride nanowires (GaN NWs) with different NW numbers (i.e., 1–100) and diameters (i.e., 220–640 nm) fabricated on the same wafer substrate to prove the feasibility of employing the vertical 3D architecture concept towards massively parallel electronic integration, particularly for logic circuitry and metrological applications. A top-down approach combining both inductively coupled plasma dry reactive ion etching (ICP-DRIE) and wet chemical etching is applied in the realization of vertically aligned GaN NWs on metalorganic vapor-phase epitaxy (MOVPE)-based GaN thin films with specific doping profiles. The FETs are fabricated involving a stack of n-p-n GaN layers with embedded inverted p-channel, top drain bridging contact, and wrap-around gating technology. From the electrical characterization of the integrated NWs, a threshold voltage (Vth) of (6.6 ± 0.3) V is obtained, which is sufficient for safely operating these devices in an enhancement mode (E-mode). Aluminium oxide (Al2O3) grown by atomic layer deposition (ALD) is used as the gate dielectric material resulting in nearly-zero gate hysteresis (i.e., forward and backward sweep Vth shift (ΔVth) of 0.2 V). Regardless of the required device processing optimization for having better linearity profile, the upscaling capability of the devices from single NW to NW array in terms of the produced currents could already be demonstrated. Thus, the presented concept is expected to bridge the nanoworld into the macroscopic world, and subsequently paves the way to the realization of innovative large-scale vertical GaN nanoelectronics.
CRIS-Team Scopus Importer:2021-06-11

Toward frequency-domain modeling of mode locking in semiconductor lasers - Kreuter, Philipp; Witzigmann, Bernd; Fichtner, Wolfgang (IEEE Journal of Selected Topics in Quantum Electronics, 2011)
In this paper, a frequency-domain harmonic balance method is developed for solving the Maxwell-Bloch equations or simplified versions thereof for semiconductor lasers. The numerical algorithms are formulated to track stationary, periodic, and quasi-periodic steady-state behavior, including passive-mode-locking operation. The nonlinear set of equations with the Fourier coefficients and the fundamental angular frequency as unknowns is solved by a Newton method. Special focus is put on the derivation of a comprehensive bifurcation analysis tool including homotopy, continuation, stability analysis, bifurcation detection, and methods to handle branch switching. As an illustrative example of the method, nonlinear multimode characteristics of an edge-emitting laser are presented. © 2011 IEEE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Laser mode locking; nonlinear optics; semiconductor lasers; simulation

Towards nanorod LEDs: Numerical predictions and controlled growth - Koelper, Christopher; Bergbauer, Werner; Drechsel, Philipp; Sabathil, Matthias; Strassburg, Martin; Lugauer, Hans-Juergen; Witzigmann, Bernd; Fuendling, Soenke; Li, Shunfeng; Wehmann, Hergo-Heinrich; Waag, Andreas (Physica Status Solidi (C) Current Topics in Solid State Physics, 2011)
We present a numerical optimization of nanorod geometries with respect to the optical properties of an electrically driven LED emitting in the green spectral range. It is shown that an overall Purcell enhancement as well as directional emission can be achieved at an emission wavelength of 550 nm with nanorods of 110 nm radius. Position-controlled growth on patterned substrates demonstrates that the required dimensions are accessible by varying growth parameters and growth time in a large volume MOVPE reactor. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2021-06-11
Keywords: GaN; Nanorods; Nitrides; Waveguiding

Ultrafast electrically pumped VECSELs - Pallmann, W. P.; Zaugg, C. A.; Mangold, M.; Dahhan, I.; Golling, Matthias; Tilma, B. W.; Witzigmann, Bernd; Keller, Ursula (Ieee Photonics Journal, 2013)
We present an improved design for electrically pumped vertical external-cavity surface-emitting lasers (EP-VECSELs) optimized for passive modelocking with a semiconductor saturable absorber mirror (SESAM). In continuous-wave (cw) multimode operation, up to 170 mW of output power are demonstrated at a wavelength of 967 nm. Overcoming our prior limitation, we demonstrate fundamental transverse mode operation with 26 mW of average output power. Passively modelocking one of the fabricated EP-VECSELs with a quantum-well SESAM, we have achieved 6.3-ps pulses with an average output power of 6.2 mW at 1.46-GHz repetition rate, the shortest pulse duration from this type of laser to date. With slightly longer pulses of 7.3 ps, an average output power of 13 mW is obtained. Tradeoffs for further output power scaling and reduced pulse duration are discussed. © 2009-2012 IEEE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Diode lasers; Infrared lasers; Modelocked lasers; Semiconductor lasers; Ultrafast lasers

Unraveling carrier distribution in far-UVC LEDs by temperature-dependent electroluminescence measurements - Hopfner, Jakob; Kuhl, Florian; Schilling, Marcel; Muhin, Anton; Guttmann, Martin; Hofmann, Gregor; Römer, Friedhard; Wernicke, Tim; Witzigmann, Bernd; Kneissl, Michael (Applied Physics Letters, 2024)
The hole transport and the carrier distribution in AlGaN-based far-ultraviolett (UVC) light emitting diodes (LEDs) emitting around 233 nm was investigated. Temperature-dependent electroluminescence measurements on dual wavelength AlGaN multiple quantum well (MQW) LEDs show a strong shift in the spectral power distribution from 250 to 233 nm with decreasing temperature. Comparing experimental data with simulation shows that the hole mobility and the electron to hole mobility ratios have a significant influence on the carrier injection efficiency (CIE) and that the change in the spectral power distribution is originating from a change in the hole distribution in the MQWs. Poor hole injection and charge carrier confinement in the AlGaN MQW active region was identified as one of the main reasons for the low CIE in far-UVC LEDs.
CRIS-Team Scopus Importer:2024-08-30

VCSEL design for high power, densely packed arrays - Kolb, Johanna S.; Engelhardt, Andreas; Gerlach, Philipp; Jager, Roland; Monch, Holger; Weichmann, Ulrich; Witzigmann, Bernd (2013 IEEE Photonics Conference, IPC 2013, 2013)
We utilize high power VCSEL arrays for several applications where high efficiency especially at high operating temperatures is essential. Our approach to design VCSEL devices optimized for the requirements of these applications is presented. © 2013 IEEE.
CRIS-Team Scopus Importer:2021-06-11

Vertical 3D gallium nitride field-effect transistors based on fin structures with inverted p-doped channel - Strempel, Klaas; Roemer, Friedhard; Yu, Feng; Meneghini, Matteo; Bakin, Andrey; Wehmann, Hergo-Heinrich; Witzigmann, Bernd; Waag, Andreas (Semiconductor Science and Technology, 2020)
This paper demonstrates the first vertical field-effect transistor based on gallium nitride (GaN) fin structures with an inverted p-doped channel layer. A top-down hybrid etching approach combining inductively coupled plasma reactive ion etching and KOH-based wet etching was applied to fabricate regular fields of GaN fins with smooth a-plane sidewalls. The obtained morphologies are explained using a cavity step-flow model. A 3D processing scheme has been developed and evaluated via focussed ion beam cross-sections. The top-down approach allows the introduction of arbitrary doping profiles along the channel without regrowth, enabling the modulation of the channel properties and thus increasing the flexibility of the device concept. Here, a vertical npn-doping profile was used to achieve normally-off operation with an increased threshold voltage as high as 2.65 V. The p-doped region and the 3D gate wrapped around the sidewalls create a very narrow vertical electron channel close to the interface between dielectric and semiconductor, resulting in good electrostatic gate control, low leakage currents through the inner fin core and high sensitivity to the interface between GaN and gate oxide. Hydrodynamic transport simulations were carried out and show good agreement with the performed current-voltage and capacitance-voltage measurements. The simulation indicates a reduced channel mobility which we attribute to interface scattering being particularly relevant in narrow channels. We also demonstrate the existence of oxide and interface traps with an estimated sheet density of 3.2 × 1012 cm-2 related to the Al2O3 gate dielectric causing an increased subthreshold swing. Thus, improving the interface quality is essential to reach the full potential of the presented vertical 3D transistor concept.
CRIS-Team Scopus Importer:2021-06-11
Keywords: field-effect transistor; gallium nitride; nanostructures; vertical electronics

Vertical architecture for enhancement mode power transistors based on GaN nanowires - Yu, Feng; Ruemmler, D.; Hartmann, Jana; Caccamo, L.; Schimpke, T.; Strassburg, M.; Gad, A. E.; Bakin, Andrey; Wehmann, H. -H.; Witzigmann, Bernd; Wasisto, H. S.; Waag, Andreas (Applied Physics Letters, 2016)
The demonstration of vertical GaN wrap-around gated field-effect transistors using GaN nanowires is reported. The nanowires with smooth a-plane sidewalls have hexagonal geometry made by top-down etching. A 7-nanowire transistor exhibits enhancement mode operation with threshold voltage of 1.2 V, on/off current ratio as high as 108, and subthreshold slope as small as 68 mV/dec. Although there is space charge limited current behavior at small source-drain voltages (Vds), the drain current (Id) and transconductance (gm) reach up to 314 mA/mm and 125 mS/mm, respectively, when normalized with hexagonal nanowire circumference. The measured breakdown voltage is around 140 V. This vertical approach provides a way to next-generation GaN-based power devices.
CRIS-Team Scopus Importer:2021-06-11

Vertically emitting microdisk lasers - Mahler, Lukas; Tredicucci, Alessandro; Beltram, Fabio; Walther, Christoph; Faist, Jerome; Witzigmann, Bernd; Beere, Harvey E.; Ritchie, David A. (Nature Photonics, 2009)
In microdisk lasers a ring resonator is formed by successive total internal reflections inside a circularly shaped waveguide. The photon lifetime of the resulting whispering gallery optical modes is limited mainly by the waveguide absorption. Light is usually coupled out by tunnelling owing to the disk curvature or through imperfections at the border, but the output power is hard to exploit in a potential application because the emission is mainly in the disk plane and isotropic. Here we realize vertically emitting whispering gallery lasers by implementing appropriate diffraction gratings along the disk circumference. We use terahertz quantum cascade structures and demonstrate a 50-fold increase in the optical power compared to devices without gratings, while at the same time engineering the lasing spectrum according to the grating rotational symmetry. This concept will allow the fabrication of compact arrays of single-mode terahertz sources with regular beam profiles and high output power.
CRIS-Team Scopus Importer:2021-06-11

Widely tunable narrow-linewidth 1.5 μm light source based on a monolithically integrated quantum dot laser array - Becker, A.; Sichkovskyi, Vitalii; Bjelica, M.; Rippien, A.; Schnabel, F.; Kaiser, M.; Eyal, O.; Witzigmann, Bernd; Eisenstein, G.; Reithmaier, J. P. (Applied Physics Letters, 2017)
A monolithically integrated widely tunable narrow-linewidth light source was realized on an InP-based quantum dot (QD) gain material. The quasi zero-dimensional nature of QDs and the resulting low linewidth enhancement factor enabled standalone distributed feedback (DFB) lasers with intrinsic linewidths as low as 110 kHz. An integrated device comprising four DFB lasers with on-chip micro-heaters, a 3 dB-coupler network, and a semiconductor optical amplifier (SOA), which covers the entire C+ telecom band, exhibits a linewidth of below 200 kHz independent of the SOA operation current.
CRIS-Team Scopus Importer:2021-06-11

Zonal efficiency limit calculation for nanostructured solar cells - Kupec, Jan; Yu, Shuqing; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2010)
We extend the well-known Shockley-Queisser detailed balance calculation for determining the efficiency limit of a solar cell to the case of strong local deviations of the optical power absorption as present in nano-structured photovoltaic devices. In addition, the simple assumption of perfect absorption of all incident light exceeding the bandgap is refined. We present a modified Shockley-Queisser efficiency limit calculation for nano-structured photovoltaic devices, it incorporates a rigorous wave optics calculation and spatially resolved generation of electron-hole pairs. We apply this method to core-shell single-junction InP nanowire array for the use in concentrator solar cells. We investigate the efficiency limits regarding the arrangement of the active regions within the wire. Our results indicate that in a nanowire array solar cell with low volume fill factor the efficiency limit can approach the values of planar thin-film devices. This observation indicates the occurrence of micro-concentration and underlines the necessity of a wave optics approach. The spatially and spectrally resolved analysis shows that generation on the surface of the nanowires is considerable, particularly with regard to high energy photons. Therefore, it is necessary to efficiently extract those carriers. © 2010 Copyright SPIE - The International Society for Optical Engineering.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Efficiency; Limit; Nanowire; Photovoltaic; Solar cell; Solar energy; Third generation